Laminate and method for manufacturing the same

By forming a conductive lower layer and a resin layer on the semi-finished insulating resin layer and enhancing the binding force through functional group reactions, the problems of high frequency transmission loss and high production costs in the prior art are solved, and efficient and low-cost printed wiring board manufacturing is achieved.

JP2025043544APending Publication Date: 2025-04-01DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150884
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art faces transmission loss problems when manufacturing printed wiring boards with high frequency transmission requirements, especially in millimeter wave bands, and traditional methods such as coating methods have problems such as high equipment costs, low output and increased high frequency transmission losses.

Method used

A conductive lower layer and a resin layer are formed on the semi-finished insulating resin layer, and the bonding force between the two is enhanced by the reaction of specific functional groups to form a new type of circuit substrate material. The method includes forming a conductive lower layer, a resin layer and a semi-finished insulating resin layer on the temporary support layer, and enhancing the bonding force between the layers by means of hot pressing or the like.

Benefits of technology

High-quality combination between the conductive lower layer and the resin layer is achieved, the conductive performance and high-frequency transmission efficiency of the circuit substrate are improved, production costs are reduced, and output is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043544000001_ABST
    Figure 2025043544000001_ABST
Patent Text Reader

Abstract

To provide a laminate produced by a method for manufacturing a transfer laminate in which a resin layer and a plating base layer are formed on a semi-cured insulation resin layer, the laminate exhibiting excellent adhesion between a base material and the insulation resin layer and excellent adhesion between the insulation resin layer and the resin layer, and to provide a rigid printed wiring board and a molded product using the laminate.SOLUTION: After forming a plating base layer containing a conductive substance and a dispersing agent on a temporary support, functional groups of a resin layer and an insulation resin layer having a THF solution insoluble content of 1 to 80 wt% are reacted with each other to produce a transfer laminate. Using the transfer laminate, we have found that a plating base layer can be easily and inexpensively formed on a surface of a support with high quality, by peeling off only the temporary support after bonding both or only one side of a front and back surface of the support.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a printed wiring board, a high-frequency transmission printed wiring board, a rigid printed wiring board, a package substrate, an interposer, an antenna, a semiconductor chip, and the like. [Background technology]

[0002] The miniaturization and high speed of electronic devices has led to a demand for printed wiring boards with higher density and higher performance, and to meet this demand, there is a demand for printed wiring boards with a smooth surface and a sufficiently thin metal layer. Flexible copper clad laminates (hereinafter abbreviated as "FCCL") and rigid copper clad laminates (hereinafter abbreviated as "RCCL") are known as components of such printed wiring boards.

[0003] FCCL is mainly produced by a method of laminating a heat-resistant polymer film and copper foil with an epoxy resin adhesive, a method of coating the surface of copper foil with a varnish such as polyimide and drying it to form a film (casting method), a method of thermocompression bonding copper foil and a polyimide film having a thermoplastic resin layer (lamination method), a method of forming a metal film on the surface of a polyimide film by sputtering and then copper plating (sputtering method), and a method of coating the surface of a polyimide film with a primer layer, coating a metal nanoparticle layer on top of that, and copper plating using the metal nanoparticle layer as a plating base (Patent Document 1).

[0004] On the other hand, RCCL is manufactured in a number of ways: by bonding fully cured resin or ceramic to copper foil using an epoxy resin-based adhesive; by heating glass cloth impregnated with epoxy resin and bonding the copper foil to a semi-cured substrate (prepreg) by heating the glass cloth; and by coating a varnish made of a mixture of resin and inorganic filler on a release film and drying it, and then bonding the resulting resin film to the surface of the copper foil or copper wiring using thermocompression (build-up film).

[0005] However, in both FCCL and RCCL, when using copper foil, it is necessary to roughen the copper foil or substrate to ensure adhesion with the substrate or adhesive layer to be bonded. This causes problems such as transmission loss in high frequency regions such as the millimeter wave band when it comes to narrowing the pitch of printed wiring boards and the high frequency transmission required for 5G, which is currently spreading, and Beyond 5G, which is expected to expand in the future.

[0006] On the other hand, sputtering methods and coating methods that use a metal nanoparticle layer can adhere the copper plating film to the substrate with a smooth interface without roughening the substrate, so compared to methods that use copper foil, they have the advantage of making it easier to achieve narrower pitches in printed wiring boards and reducing transmission loss of high-frequency signals.

[0007] However, the sputtering method requires a large-scale vacuum facility because it uses a deposition method or a sputtering method to form a metal thin film, and the size of the substrate is limited due to the facility. In addition, when the sputtering method is applied to both sides of the substrate, the time required to create a vacuum is twice as long as when applying the sputtering method to one side, and while processing both sides one by one, defects occur on the surface of the metal layer formed by the sputtering method, resulting in a decrease in yield and high production costs. Furthermore, in order to ensure adhesion between the substrate and the metal film such as copper in the sputtering method, it is necessary to use a magnetic metal such as nickel, cobalt, or chromium, which has the disadvantage of increasing the transmission loss of high frequencies.

[0008] In order to solve these problems, a method has been developed in which a metal film layer such as a copper film is formed as a plating base layer on an uncured prepreg or build-up film, and then transferred onto a copper wiring board. However, when a metal film layer is formed on an uncured prepreg or build-up film by using a casting method, laminating method, sputtering method, or coating method, there is a problem that the uncured prepreg or build-up film hardens due to the heat history of each process, reducing the wiring embedding performance and adhesion.

[0009] On the other hand, Patent Document 2 discloses an adhesive film with a metal film having excellent peelability by forming a metal film layer and an insulating resin layer on a support including a release layer, but there is a problem in that the adhesion between the metal layer and the insulating resin layer is low.

[0010] Therefore, there has been a demand for a laminate structure and a manufacturing method that can firmly bond the metal layer and the insulating resin layer and provide excellent wiring embedding performance, adhesion, and uniform film quality. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] WO2019 / 013038 publication [Patent Document 2] WO2010 / 024370 publication Summary of the Invention [Problem to be solved by the invention]

[0012] The problem that the present invention aims to solve is to provide a laminate having excellent adhesion between a substrate and the insulating resin layer, between the insulating resin layer and the resin layer, and between the resin layer and the plating base layer, using a manufacturing method for a laminate in which a plating base layer and a resin layer are formed on a semi-cured insulating resin layer, and to provide a laminate having excellent adhesion between a substrate and the insulating resin layer, between the insulating resin layer and the resin layer, and between the resin layer and the plating base layer, and a rigid printed wiring board and a molded product using the same. [Means for solving the problem]

[0013] As a result of intensive research to solve the above problems, the present inventors have produced a laminate by forming a plating underlayer containing a conductive material and a dispersant on a temporary support, and then reacting functional groups of a resin layer and an insulating resin layer having a THF solution insoluble content of 1 to 80% by weight thereon. In addition, the inventors have found that a plating underlayer can be easily, inexpensively, and with high quality formed on the surface of a support by laminating both the front and back sides of the support or only one side of the support using this laminate, and then peeling off only the temporary support, thereby completing the present invention.

[0014] Specifically, the present invention relates to 1. A laminate characterized by having, on at least one surface of a temporary support (A), a plating underlayer (B) containing a dispersant (b1) and a conductive substance (b2), a resin layer (C), and an insulating resin layer (D) having a THF solution insoluble content of 1 to 80% by weight. 2. The laminate according to 1, characterized in that the surface of the laminate on which the insulating resin layer (D) is formed is attached to at least one surface of a support (E). 3. The laminate according to 1 or 2, characterized in having a resin layer (C), a plating underlayer (B), and a temporary support (A) on both sides of the insulating resin layer (D) in that order. 4. The laminate according to any one of 1 to 3, further comprising a metal plating layer (F) on the plating underlayer (B) of the laminate. 5. The laminate according to any one of 1 to 4, wherein the resin layer (C) is a compound (c1) having a functional group [X], and the insulating resin layer (D) is a compound (d1) having a functional group [Y], thereby forming a chemical bond. 6. The laminate according to any one of 1 to 5, wherein the functional group [X] contained in the resin layer (C) has at least one of an epoxy group and an amino group. 7. A laminate according to any one of 1 to 6, characterized in that the functional group [Y] contained in the insulating resin layer (D) has at least one of an epoxy group, a maleimide group, a vinylbenzyl group, an acrylate group, a methacrylate group, a carbonyl group, and a hydroxyl group. 8. The laminate according to any one of 1 to 7, wherein the insulating resin layer (D) contains an inorganic compound (x). 9. The laminate according to any one of 1 to 8, wherein the plating underlayer (B) is one or more layers. 10. The laminate according to any one of 1 to 9, wherein the resin layer (C) is one or more layers. 11. The laminate according to any one of 1 to 10, wherein the insulating resin layer (D) is one or more layers. 12. The laminate according to any one of 1 to 11, wherein the resin layer (C) has a glass transition temperature (Tg) higher than the insulating resin layer (D). 13. The laminate according to any one of 1 to 12, wherein the dispersant (b1) has a basic nitrogen atom-containing group. 14. The laminate according to any one of 1 to 13, wherein the conductive substance (b2) is silver. 15. The thickness of the plating underlayer (B) is 1 to 10,000 mg / m 2 15. The laminate according to any one of 1 to 14, 16. The laminate according to any one of 1 to 15, wherein the resin layer (C) has a thickness of 0.01 to 100 μm. 17. The laminate according to any one of claims 116, characterized in that the insulating resin layer (D) has a thickness of 1 to 1000 µm. 18. The laminate according to any one of 4 to 17, wherein the metal plating layer (F) has a thickness of 0.05 to 1000 μm. 19. A method for producing a laminate according to any one of 1 to 18, characterized in that a plating underlayer (B), a resin layer (C) and an insulating resin layer (D) are successively formed on a temporary support (A). 20. Step 1 of producing a laminate in which a plating underlayer (B), a resin layer (C) and an insulating resin layer (D) are successively formed on a temporary support (A); Step 2: bonding the surface of the laminate on which the insulating resin layer (D) is formed to at least one surface of a support (E); A step 3 of peeling off the temporary support (A) of the laminate bonded to the support (E) and forming the insulating resin layer (D), the resin layer (C) and the plating underlayer (B) on at least one surface of the support (E); Step 4 of forming a metal plating layer (F) on the surface of the plating underlayer (B); 20. The method for producing a laminate according to any one of 1 to 19, comprising the steps of: 21. A printed wiring board, a package substrate, an interposer, a wiring substrate for LED electrodes, or a photonics-electronics hybrid device, comprising the laminate according to any one of 1 to 18. Effect of the Invention

[0015] The laminate of the present invention is a product obtained by forming a plating underlayer on a temporary support, and then forming a resin layer and an insulating resin layer, thereby causing a reaction between the functional groups of the resin layer and the insulating resin layer. In addition, by laminating this laminate on both sides of a support at once, the method for producing a conductive pattern can easily form a resin layer and a plating underlayer on a support with high quality, simply, inexpensively, and more easily than conventional coating methods using metal nanoparticle layers.

[0016] The method for producing a conductive pattern of the present invention can be suitably used as electronic components such as, for example, printed wiring boards, rigid printed wiring boards, flexible printed wiring boards, package substrates, ceramic substrates, glass substrates, silicon wafer substrates, metal substrates, conductive films for touch panels, metal meshes for touch panels, organic solar cells, organic EL elements, organic transistors, RFID such as non-contact IC cards, electromagnetic wave shields, LED lighting substrates, digital signage, etc. In particular, it is most suitable for rigid printed wiring boards and flexible printed wiring boards.

[0017] In addition, by applying it to molded products, it can be suitably used for decoration of electronic components such as molded circuit boards (MIDs), connectors for connecting wiring for optical communications, etc., electrical components, peripheral components for electric motors, and battery components; decorative parts for automobiles, lamp reflectors, mobile phones, personal computers, mirrors, containers, home appliances, various switches, faucet parts, shower heads, etc. [Brief description of the drawings]

[0018] [Figure 1] The graph shows the results of applying a fluid containing silver as the conductive material (b2) to a temporary support (A) and then drying the coating, followed by measuring the coating by glow discharge optical emission spectroscopy. [Diagram 2] The conductive material (b2) is silver, and the fluid having a different composition from that in FIG. 1 is applied to a temporary support (A), and the dried coating is measured by glow discharge optical emission spectroscopy. [Diagram 3]1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one surface of a temporary support. [Figure 4] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, and then laminated to one side of a base material. [Diagram 5] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, and then bonded to both sides of a substrate. [Figure 6] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, which is then bonded to one side of a base material, and the temporary support is then peeled off. [Figure 7] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, which are then laminated to both sides of a base material, and the temporary support is then peeled off. [Figure 8] FIG. 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are sequentially formed on one side of a temporary support, which is then bonded to one side of a base material, the temporary support is then peeled off, and a metal plating layer is then formed. [Figure 9] FIG. 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are sequentially formed on one side of a temporary support, which is then bonded to both sides of a base material, the temporary support is then peeled off, and a metal plating layer is then formed. [Figure 10] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, and then laminated to one side of a wiring board. [Figure 11] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, and then bonded to both sides of a wiring board. [Figure 12] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, which is then bonded to one side of a wiring board, and the temporary support is then peeled off. [Figure 13] 1 is a cross-sectional view of a laminate of the present invention in which a plating underlayer, a resin layer, and an insulating resin layer are successively formed on one side of a temporary support, which is then bonded to both sides of a wiring board, and then the temporary support is peeled off. [Figure 14] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, which is then bonded to one side of a wiring board, the temporary support is then peeled off, and a metal plating layer is then formed. [Figure 15] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, which is then bonded to both sides of a wiring board, the temporary support is then peeled off, and a metal plating layer is then formed. [Figure 16] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, which is then bonded to one side of a wiring board, the temporary support is peeled off, and wiring processing is then performed. [Figure 17] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, which is then bonded to both sides of a wiring board, the temporary support is then peeled off, and wiring processing is then performed. [Figure 18] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are sequentially formed on one side of a temporary support, and the resulting laminate is bonded to the insulating resin layer side and the resin layer side of a laminate in which a plating base layer and a resin layer are sequentially formed on one side of a temporary support. [Figure 19] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, the insulating resin layer side and the resin layer side of the laminate are bonded to each other, and the temporary support is then peeled off. [Figure 20] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, the resulting laminate is bonded to the insulating resin layer side and the resin layer side of the temporary support, the temporary support is peeled off, and a metal plating layer is formed. [Figure 21] This is a cross-sectional view of the laminate of the present invention, in which a plating base layer, a resin layer, and an insulating resin layer are formed in sequence on one side of a temporary support, the insulating resin layer side and the resin layer side are bonded to a laminate in which a plating base layer and a resin layer are formed in sequence on one side of a temporary support, and then the temporary support is peeled off and wiring processing is performed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention relates to a laminate in which a plating underlayer (B) containing a dispersant (b1) and a conductive material (b2) is formed on at least one surface of a temporary support (A), and then a resin layer (C) containing a compound (c1) having a functional group [X] and an insulating resin layer (D) containing a compound (d1) having a functional group [Y] are sequentially laminated on at least one surface of the temporary support (A), in which a bond is formed by reacting the functional group [X] of the compound (c1) contained in the resin layer (C) with the functional group [Y] of the compound (d1) contained in the insulating resin layer (D), and a method for producing the laminate.

[0020] The present invention is also a method for producing a conductive pattern, characterized by comprising step 1 of bonding the surface of the laminate on which the insulating resin layer (D) is formed to at least one surface of a support (E), and step 2 of peeling off the temporary support (A) of the bonded laminate, and forming the insulating resin layer (D), the resin layer (C), and the plating base layer (B) on at least one surface of the support (E).

[0021] The laminate of the present invention may be a laminate in which the plating base layer (B), the resin layer (C), and the insulating resin layer (D) are sequentially laminated on at least one surface of a temporary support (A), or may be a laminate in which the plating base layer (B), the resin layer (C), and the insulating resin layer (D) are sequentially laminated on both surfaces of the temporary support (A).

[0022] The temporary support (A) is required to be peeled off after laminating the laminate. Examples of the temporary support (A) include polymer films such as aromatic polyesters, such as polyethylene terephthalate, polybutylene terephthalate (PBT), polyethylene naphthalate, and polybutylene naphthalate; fluorine-based resins, such as polytetrafluoroethylene, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride resin, trifluorochloroethylene resin, trifluorochloroethylene-ethylene copolymer, tetrafluoroethylene-perfluorodioxysol copolymer, vinyl fluoride resin, and polyvinylidene fluoride; polymethylpentene (TPX), polypropylene (PP) [including biaxially oriented polypropylene (OPP) and nonaxially oriented polypropylene (CPP)], and polyethylene (PE). Examples of the temporary support include olefin resins such as high density polyethylene (HDPE), low density polyethylene (LDPE), and linear low density polyethylene (LLDPE); polystyrene (PS); polyimide resins such as polyvinyl chloride (PVC), polyimide, and transparent polyimide; polyamide resins such as polyamideimide and polyamide; polycarbonate, acrylonitrile-butadiene-styrene (ABS) resin, polymer alloy of ABS and polycarbonate, acrylic resins such as poly(methyl meth)acrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polycarbonate, polyethylene, polypropylene, polyurethane, liquid crystal polymer (LCP), polyether ether ketone (PEEK), polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), and epoxy resins. Among these, aromatic polyester, polyethylene, olefin resin, fluorine-based resin, polyimide resin, LCP, and polyphenylene sulfide are preferably used as the temporary support.

[0023] In addition, metals can be used as the temporary support (A), and examples of the metals that can be used include copper, aluminum, aluminum alloys, titanium, stainless steel, beryllium copper, phosphor bronze, nickel, nichrome, nickel alloys, tin, zinc, lead, gold, zinc, lead, tantalum, molybdenum, niobium, iron, and silver. In addition, inorganic substrates can be used as the temporary support (A) made of silicon, ceramics, glass, and the like. Among these, it is preferable to use copper and aluminum as the temporary support.

[0024] The shape of the temporary support (A) is not particularly limited, but a film or sheet is easy to handle. The film thickness of the temporary support (A) is usually preferably in the range of 1 to 5,000 μm, more preferably in the range of 1 to 300 μm, more preferably in the range of 1 to 200 μm, more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 50 μm. The temporary support (A) is attached to the support (E) described later, and after the plating underlayer (B), the resin layer (C), and the insulating resin layer (D) are laminated on the support (E), it is unnecessary, so it is preferably thin enough not to impair workability.

[0025] The surface of the temporary support (A) is preferably smooth so as to facilitate the transfer of the plating underlayer (B), the resin layer (C) and the insulating resin layer (D) from the laminate. Specifically, the surface roughness (maximum height Sz) measured by a laser microscope is preferably in the range of 0.001 to 30 μm, more preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. The surface roughness (maximum height Sz) is measured by the evaluation method described in ISO 25178 and represents the distance from the highest point to the lowest point on the surface.

[0026] In addition, a release layer formed on the surface of the temporary support (A) can be used. The release layer can be formed by applying a silicone-based release agent or a non-silicone-based release agent to the temporary support (A). As the non-silicone-based release agent, an alkyd resin, a melamine resin, an acrylic resin, a cellulose resin, a urea resin, a polyolefin, a paraffin, a silica composite acrylic resin, a silica composite melamine resin, a silica composite urethane resin, a silica composite epoxy-based resin, a silica composite phenolic resin, a silica composite popar resin, a silica composite polystyrene-based resin, a silica composite polyvinyl acetate-based resin, a silica composite polyimide-based resin, and a silica composite polyamideimide-based resin can be used. When the temporary support (A) of the transfer film is peeled off, the silicone resin of the release layer of the silicone resin migrates to the surface of the plating base layer (B), and when a plating layer is formed on the plating base layer (B) described later, the silicone resin inhibits the adhesion between the plating base layer (B) and the metal plating layer (F). For this reason, it is preferable to use a non-silicone release agent for the release layer, and it is preferable to use an acrylic resin, a melamine resin, or a urethane resin.

[0027] The thickness of the release layer is not particularly limited as long as it can secure releasability, but it is preferably a thin film in order to prevent the release layer from adhering to the surface of the plating underlayer (B) described later. Specifically, the thickness is preferably 0.01 to 50 μm, more preferably 0.01 to 10 μm, and even more preferably 0.01 to 1 μm.

[0028] It is preferable to use a metal as the temporary support (A). When forming the plating underlayer (B) using metal nanoparticles on the surface of the temporary support (A) described later, the plating underlayer (B) can be dried at a higher temperature than when a polymer film is used, and the surface resistance of the plating underlayer (B) can be reduced, thereby increasing the conductivity of the plating underlayer itself. In addition, in the process of forming a conductive pattern, after bonding the surface of the insulating resin layer (D) of the laminate described later to the support (E), when forming through holes penetrating both sides from the surface of the temporary support (A) or non-through holes to the conductive pattern of the inner layer, holes are formed with a drill or laser, but when a polymer film is used as the temporary support (A), polymer smears may occur during hole drilling, and plating precipitation problems may occur in the process of making the through holes or non-through holes conductive. On the other hand, when a metal is used, a conventional drilling method using a drill or laser for a printed circuit board can be applied, and it is preferable to use copper or aluminum as the temporary support (A).

[0029] When the plating underlayer (B) described later is applied to the temporary support (A), the surface of the temporary support (A) may be subjected to a surface treatment, if necessary, for the purpose of making the surface of the temporary support (A) more easily wettable with a coating material. Specifically, methods such as plasma discharge treatment such as corona discharge treatment, dry treatment such as ultraviolet treatment, and wet treatment using water, an aqueous solution of an acid or alkali, or an organic solvent, etc., may be mentioned. If the temporary support (A) is subjected to an excessive surface treatment, peeling at the interface between the temporary support (A) and the plating underlayer (B) described later becomes difficult, so it is preferable to perform the surface treatment appropriately.

[0030] Next, the plating underlayer (B) will be described. The plating underlayer (B) is a layer containing a dispersant (b1) and a conductive substance (b2). When the plating underlayer is formed on the temporary support (A) by the method described below, the dispersant (b1) can be localized at the interface between the plating underlayer (B) and air and at the interface between the plating underlayer (B) and the temporary support (A).

[0031] The interface between the plating underlayer (B) and air is the surface on which the resin layer (C) described later is formed, and the localization of a large amount of the dispersant (b1) at the air interface facilitates the formation of chemical bonds between the functional group of the dispersant (b1) and the functional group of the compound (c1) contained in the resin layer (C), improving the adhesion between the plating underlayer (B) and the resin layer (C). On the other hand, the interface between the plating underlayer (B) and the temporary support (A) is the surface on which the metal plating layer (F) is formed after the transfer laminate described later is transferred to the support (E), and therefore if there is a large amount of localized dispersant (b1), the adhesion between the plating underlayer (B) and the metal plating layer (F) is reduced.

[0032] Therefore, as a result of extensive investigation, the presence of carbon atoms derived from the dispersant (b1) was measured using glow discharge optical emission spectroscopy after forming a plating underlayer (B) on a temporary support (A). It was found that there is an optimal amount of carbon atoms at the interface between the plating underlayer (B) and air (ultimately on the resin layer (C) side) and at the interface between the plating underlayer (B) and temporary support (A) (ultimately on the metal plating layer (F) side).

[0033] Glow discharge optical emission spectroscopy is a method for measuring the element distribution in the depth direction of the plating underlayer (B) by high-frequency sputtering the plating underlayer (B) in an argon glow discharge region and continuously analyzing the emission lines of the sputtered atoms. For glow discharge optical emission spectroscopy, a high-frequency glow discharge optical emission surface analyzer (GDS) GD-Profiler2 manufactured by HORIBA, Ltd. can be used. The measurement conditions were argon gas, gas pressure 1000 Pa, power 20 W, and anode diameter 4 mm. Note that the signal intensity obtained by the measurement of glow discharge optical emission spectroscopy is the emission intensity of each element obtained simultaneously from each independent detector, so in order to quantify each element, it is necessary to create a calibration curve for each element. However, if one element is focused on, an element profile in the depth direction of the plating underlayer (B) can be obtained from the signal intensity.

[0034] 1 and 2 show the results of glow discharge optical emission spectroscopy when silver is used as the conductive material (b2). FIG. 1 is a graph with the sputtering time on the horizontal axis and the signal intensity of each element on the vertical axis. In the profile of silver atoms, it can be seen that there is a large amount of carbon atoms at the interface between the air and the plating underlayer (B) (finally on the resin layer (C) side) at about 0.5 seconds after the start of sputtering. Thereafter, the number of carbon atoms decreases as the sputtering time elapses. This indicates that there are relatively few carbon atoms inside the plating underlayer (B). When sputtering is further advanced, there is an interface between the plating underlayer (B) and the temporary support (A) (finally on the metal plating layer (F) side) at about 16 seconds after the start of sputtering, where there are many carbon atoms. Therefore, since there are many carbon atoms derived from the dispersant (b1) at the interface between the air and the plating underlayer (B), it can be seen that the functional group of the dispersant (b1) reacts with the functional group of the compound (c1) contained in the resin layer (C) described later, and chemical bonds are easily formed.

[0035] Figure 2 shows a plating underlayer (B) different from that in Figure 1 formed on a temporary support (A). In the profile of silver atoms, many carbon atoms are present at the interface between the air and the plating underlayer (B) (ultimately on the resin layer (C) side) about 1 second after the start of sputtering, and thereafter, even as the sputtering time passes, the signal intensity of the carbon atoms does not change. At about 21 seconds into the sputtering time, when the signal intensity of the silver atoms drops, there is no increase in the number of carbon atoms at the interface between the plating underlayer (B) and the temporary support (A) (ultimately on the metal plating layer (F) side), but no increase in the number of carbon atoms is observed.

[0036] The plating underlayer (B) may be a layer provided on the entire surface of the temporary support (A), or may be a layer provided on a part of the surface of the temporary support (A). Specific examples of the plating underlayer (B) present on a part of the surface of the temporary support (A) include a conductive pattern formed on the surface of the temporary support (A) using a pattern resist, a conductive pattern in which the plating underlayer (B) is formed only on the necessary parts using a printing method, and a conductive pattern obtained by forming the plating underlayer (B) on the entire surface of the temporary support (A) and then removing (trimming) the unnecessary parts with a laser or the like to leave only the necessary parts.

[0037] The plating underlayer (B) contains, relative to the entire plating underlayer (B), the conductive substance (b2) in a range of 80 mass % to 99.9 mass % and the dispersant (b1) in a range of 0.1 mass % to 20 mass %, more preferably 0.1 mass % to 10 mass %.

[0038] A compound having a basic nitrogen atom-containing group or a phosphate ester group is used as the dispersant (b1) contained in the plating underlayer (B), and is reacted with a functional group of a compound (c1) contained in the resin layer (C) described below to form a chemical bond. The basic nitrogen atom-containing group or the phosphate ester group may react partially with the functional group to form a chemical bond, or may react entirely with the functional group to form a chemical bond.

[0039] Examples of the basic nitrogen atom-containing group include an imino group, a primary amino group, and a secondary amino group.

[0040] When a dispersant (b1) having multiple basic nitrogen atom-containing groups in its molecule is used, it is preferable in terms of improving adhesion between the plating underlayer (B) and the resin layer (C) that one of the basic nitrogen atom-containing groups participates in bonding with a functional group of a compound (c1) contained in the resin layer (C) described below when the plating underlayer (B) is formed, and the other contributes to interaction with a conductive material (b2) such as silver in the plating underlayer (B).

[0041] The dispersant (b1) having a basic nitrogen-containing group is preferably a polymer dispersant because it can improve the adhesion between the plating underlayer (B) and the metal plating layer (F) described later by making the plating underlayer (B) porous. As the polymer dispersant, it is preferable to use a polyalkyleneimine such as polyethyleneimine or polypropyleneimine, or a compound in which polyoxyalkylene is added to the polyalkyleneimine. By using a polymer dispersant as the dispersant, the dispersant in the plating underlayer (B) can be removed to make it porous, and the void size can be increased, and voids of nano to submicron order sizes can be formed, compared to low molecular weight dispersants. The voids are easily filled with the metal constituting the metal plating layer (F) described later, and the filled metal becomes an anchor, and the adhesion between the plating underlayer (B) and the metal plating layer (F) described later can be greatly improved.

[0042] When using a dispersant (b1) having a phosphate ester group in the molecule, it is preferable to use an acrylic resin into which the phosphate ester group can be easily introduced. When introducing a phosphate ester group into an acrylic resin, a monomer having a phosphate ester group is used as a raw material for the acrylic resin. Examples of monomers having a phosphate ester group include 2-((meth)acryloyloxy)ethyl phosphate, 2-((meth)acryloyloxy)propyl phosphate, diphenyl(2-acryloyloxyethyl) phosphate, diphenyl(2-methacryloyloxyethyl)phosphate, and phenyl(2-acryloyloxyethyl)phosphate.

[0043] In addition, it is preferable to use a functional group other than the phosphate group in the dispersant (b1) in order to improve the adhesion between the plating underlayer (B) and the resin layer (C). For example, the functional group may be a carboxyl group, an isocyanate group, a blocked isocyanate group, an epoxy group, a hydroxyl group, an oxazoline group, an N-methylol group, an N-alkoxymethyl group, an amino group, an alkoxysilyl group, etc. In addition, the dispersant (b1) may have two or more of these functional groups.

[0044] The content of the functional group in the dispersion material (b1) is preferably in the range of 0.001 to 5 mmol / g, more preferably in the range of 0.01 to 3 mmol / g, and even more preferably in the range of 0.01 to 2 mmol / g, because this can further improve adhesion to the resin layer (C).

[0045] The conductive material (b2) constituting the plating underlayer (B) includes transition metals or their compounds, among which ionic transition metals are preferred. Examples of the ionic transition metals include copper, silver, gold, nickel, palladium, platinum, cobalt, and the like. Among these, silver and copper are preferred because they are easy to form the metal plating layer (F) described below, and it is more preferred to use silver because it reduces the surface resistance of the plating underlayer. In addition, magnetic metals such as nickel and cobalt reduce the transmission characteristics required for high-frequency transmission, so it is preferred to use silver or copper, and it is more preferred to use silver.

[0046] The conductive material (b2) used to form the plating underlayer (B) is preferably particulate or fibrous. When the conductive material (b2) is particulate, the size of the particles is preferably nano-sized. Specifically, the average particle size is preferably 1 to 100 nm, more preferably 1 to 50 nm, because this makes it possible to form a denser coating film and further reduce the resistance value. The average particle size can be measured using "Nanotrac UPA-150" manufactured by Microtrac.

[0047] On the other hand, when the conductive substance (b2) is in the form of fibers, the diameter of the fibers is preferably 5 to 100 nm, more preferably 5 to 50 nm, in order to form a denser coating film and further reduce the resistance value, and the length of the fibers is preferably 0.1 to 100 μm, more preferably 0.1 to 30 μm.

[0048] The plating underlayer (B) can be formed by preparing a fluid containing the dispersant (b1) and the conductive material (b2) and applying the fluid. The content of the conductive material (b2) in the fluid is preferably in the range of 1 to 90% by mass, more preferably in the range of 1 to 60% by mass, and even more preferably in the range of 1 to 10% by mass.

[0049] Examples of components that may be blended into the fluid include dispersants and solvents for dispersing the conductive material (b2) in a solvent, and, if necessary, surfactants, leveling agents, viscosity modifiers, film-forming aids, antifoaming agents, preservatives, etc., which will be described later.

[0050] A dispersant may be used in combination to disperse the conductive material (b2) in the solvent. Examples of the dispersant include dodecanethiol, 1-octanethiol, triphenylphosphine, dodecylamine, polyethylene glycol, polyvinylpyrrolidone, polyethyleneimine, polyvinylpyrrolidone, fatty acids such as myristic acid, octanoic acid, and stearic acid, polycyclic hydrocarbon compounds having a carboxyl group such as cholic acid, glycyrrhizic acid, and abietic acid, urethane resins, acrylic resins, and compounds containing a phosphoric acid group in the urethane resins or acrylic resins.

[0051] The amount of the dispersant used to disperse the conductive substance (b2) is preferably in the range of 0.01 to 50 parts by mass, and more preferably in the range of 0.01 to 10 parts by mass, per 100 parts by mass of the conductive substance (b2).

[0052] When the dispersant is removed by firing to form a porous plating underlayer (B) for the purpose of further improving the adhesion between the plating underlayer (B) and the metal plating layer (F) described later, the content of the conductive material (b2) is preferably in the range of 0.1 to 10 parts by mass, more preferably in the range of 0.1 to 5 parts by mass, per 100 parts by mass of the conductive material (b2).

[0053] The solvent used for the fluid may be an aqueous medium or an organic solvent. Examples of the aqueous medium include distilled water, ion-exchanged water, pure water, and ultrapure water. Examples of the organic solvent include alcohol compounds, ether compounds, ester compounds, and ketone compounds.

[0054] Examples of the alcohol compound include methanol, ethanol, n-propanol, isopropyl alcohol, n-butanol, isobutyl alcohol, sec-butanol, tert-butanol, heptanol, hexanol, octanol, nonanol, decanol, undecanol, dodecanol, tridecanol, tetradecanol, pentadecanol, stearyl alcohol, allyl alcohol, cyclohexanol, terpineol, terpineol, dihydroterpineol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, and tripropylene glycol monobutyl ether.

[0055] In addition to the solvent, the fluid may contain ethylene glycol, diethylene glycol, 1,3-butanediol, isoprene glycol, glycerin, or the like, if necessary.

[0056] As the surfactant, a general surfactant can be used, and examples thereof include di-2-ethylhexyl sulfosuccinate, dodecylbenzenesulfonate, alkyldiphenyletherdisulfonate, alkylnaphthalenesulfonate, and hexametaphosphate.

[0057] As the leveling agent, a general leveling agent can be used, and examples thereof include silicone-based compounds, acetylene diol-based compounds, and fluorine-based compounds.

[0058] As the viscosity modifier, a general thickening agent can be used, and examples thereof include acrylic polymers and synthetic rubber latexes which can be thickened by adjusting the alkalinity, urethane resins which can be thickened by molecular association, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, polyvinyl alcohol, water-added castor oil, amide wax, oxidized polyethylene, metal soaps, and dibenzylidene sorbitol.

[0059] As the film-forming aid, a general film-forming aid can be used, for example, anionic surfactants (such as dioctyl sulfosuccinate sodium salt), hydrophobic nonionic surfactants (such as sorbitan monooleate), polyether-modified siloxane, silicone oil, etc.

[0060] As the defoaming agent, a general defoaming agent can be used, and examples thereof include silicone-based defoaming agents, nonionic surfactants, polyethers, higher alcohols, polymer surfactants, and the like.

[0061] As the preservative, a general preservative can be used, and examples thereof include isothiazolinone-based preservatives, triazine-based preservatives, imidazole-based preservatives, pyridine-based preservatives, azole-based preservatives, and pyrithione-based preservatives.

[0062] The viscosity of the fluid (measured at 25° C. using a Brookfield viscometer) is preferably in the range of 0.1 to 500,000 mPa s, and more preferably in the range of 0.2 to 10,000 mPa s. When the fluid is applied (printed) by a method such as inkjet printing or letterpress reverse printing, which will be described later, the viscosity is preferably in the range of 5 to 20 mPa s.

[0063] As a method for producing the laminate of the present invention, first, a fluid containing a dispersant (b1) and a conductive substance (b2) is applied onto a temporary support (A), and organic solvents and the like contained in the fluid are removed by drying to form a plating underlayer (B), and then a fluid containing a compound (c1) having a functional group is applied to form a resin layer (C), and then a bond is formed by reacting a basic nitrogen atom-containing group or a phosphate ester group of the dispersant (b1) contained in the plating underlayer (B) with a functional group of the compound (c1) contained in the resin layer (C).

[0064] Examples of the method for coating or printing the fluid on the temporary support (A) include inkjet printing, reverse printing, screen printing, offset printing, gravure printing, flexographic printing, pad printing, spin coating, spray coating, bar coating, die coating, slit coating, roll coating, dip coating, rotary coating, capillary coating, microgravure coating, and doctor roll methods.

[0065] The plating underlayer (B) may be formed in one layer or in two or more layers. When two or more plating underlayers (B) are formed, for example, a coating defect of the plating underlayer formed in the first layer can be filled by the second layer, thereby forming a more homogeneous film.

[0066] The drying temperature after coating or printing the fluid containing the dispersant (b1) and the conductive material (b2) is preferably in the range of 50°C to 400°C, more preferably in the range of 80°C to 340°C, preferably in the range of 120°C to 320°C, preferably in the range of 150°C to 300°C, and further preferably in the range of 180°C to 280°C.

[0067] The drying may be performed by blowing air or may not require blowing air. The drying may be performed in the air, in an atmosphere substituted with an inert gas such as nitrogen or argon, or under an air flow, or in a vacuum. When the plating underlayer (B) is a layer using metal nanoparticles dispersed with a dispersant, the layer of metal nanoparticles is oxidized by drying in the air, and the adhesion with the metal plating layer (F) described later can be improved. In addition, by drying in the air, the dispersant, surfactant, leveling agent, viscosity modifier, film-forming assistant, defoamer, preservative, etc. present on the surface of the plating underlayer (B) can be oxidized and decomposed, and the compounds that inhibit adhesion can be reduced, so that the adhesion between the plating underlayer (B) and the metal plating layer (F) can be improved.

[0068] The mass per unit area of ​​the plating underlayer (B) is 1 to 30,000 mg / m 2 The range is preferably 1 to 5,000 mg / m 2 In the case where electroless plating is performed on the plating underlayer (B), the plating underlayer (B) is used as a catalyst, so the thickness of the plating underlayer may be thin, specifically, 1 to 5000 mg / m 2 is preferable, and 10 to 1000 mg / m 2 is preferable, and 10 to 500 mg / m 2 is preferable, and 50 to 500 mg / m 2 On the other hand, when electrolytic plating is performed on the plating underlayer (B), it is preferable that the plating underlayer (B) has conductivity and low resistance, so that the film thickness is preferably thicker, and is preferably 100 to 30,000 mg / m 2 is preferable, and 100 to 10,000 mg / m 2 is preferable, and 300 to 5000 mg / m 2 is preferable. In order to improve the adhesion between the metal plating layer (F) and the plating underlayer (B) described later and to reduce the cost by thinning the expensive plating underlayer (B), the thickness of the plating underlayer (B) is preferably 500 to 2000 mg / m 2 is more preferred.

[0069] When electrolytic plating is performed on the plating underlayer (B), the surface resistance of the plating underlayer (B) is preferably low in order to form the electrolytic plating uniformly. The surface resistance is preferably in the range of 0.1 to 10,000 Ω / □, more preferably in the range of 0.15 to 1000 Ω / □, more preferably in the range of 0.15 to 500 Ω / □, more preferably in the range of 0.2 to 100 Ω / □, more preferably in the range of 0.2 to 10 Ω / □, and even more preferably in the range of 0.2 to 5 Ω / □.

[0070] Next, the resin layer (C) will be described. The resin layer (C) is a layer provided for the purpose of improving adhesion between the plating underlayer (B) and an insulating resin layer (D) described below.

[0071] The resin layer (C) forms a chemical bond by reacting a functional group of the compound (c1) present in a coating film formed on the surface of the plating underlayer (B) by coating, drying, etc., with the dispersant (b1) contained in the plating underlayer (B). The reaction proceeds even at room temperature and forms a chemical bond, but the reaction proceeds further by heating and forms a chemical bond.

[0072] In addition, the resin layer (C) is formed by applying and drying a compound (c1) containing a functional group [X] (c1), and the functional group of the compound (c1) present in the coating film (c) forms a chemical bond with a functional group of a compound (d1) having a functional group [Y] contained in the insulating resin layer (D) described below. By heating and drying during the formation of the coating film of the insulating resin layer (D) described below, the reaction proceeds further and a chemical bond is formed.

[0073] This increases adhesion at the interface between the plating base layer (B) and the resin layer (C) and at the interface between the resin layer (C) and the insulating resin layer (D) described later. When the laminate is bonded to the support (E) described later and the temporary support (A) of the laminate is peeled off, the plating base layer (B) and the resin layer (C), and the resin layer (C) and the insulating resin layer (D) described later do not easily peel off. Furthermore, in a configuration in which the insulating resin layer (D), the resin layer (C), and the plating base layer (B) described later are laminated on the support (E) described later, a conductive pattern with excellent adhesion that does not cause peeling over time can be obtained.

[0074] The coating film (c), which can be said to be a precursor of the resin layer (C), is formed by applying a composition containing a compound (c1) having a functional group [X] to the surface of a support, followed by drying, etc. The compound (c1) contained in the coating film (c) has a functional group [X] that reacts with a compound (d1) having a functional group [Y] contained in the insulating resin layer (D) described below.

[0075] Examples of the functional group [X] that reacts with the functional group [Y] contained in the insulating resin layer (D) described later include an amino group, an epoxy group, a vinyl group, an acrylate group, a methacrylate group, a hydroxyl group, a carbonyl group, a carboxyl group, an aldehyde group, a nitro group, an imino group, a sulfo group, a thiol group, an isocyanate group, a blocked isocyanate group, an oxazoline group, an N-methylol group, an N-alkoxymethyl group, an alkoxysilyl group, etc. Among these, an amino group or an epoxy group reacts as the functional group [Y] as the functional group [X], and an amino group and an epoxy group react with each other to form a strong resin layer.

[0076] The functional group [X] is present in an amount of preferably 50 mmol / kg to 10,000 mmol / kg, more preferably 100 mmol / kg to 8,000 mmol / kg, and even more preferably 100 mmol / kg to 5,000 mmol / kg, relative to the entire resin layer (C), in order to further improve adhesion.

[0077] Examples of the curing agent having an amino group used for the functional group [X] include metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiphenylether, 4-aminophenyl 4-aminobenzoate, 2,2'-bis(trifluoromethyl)benzidine, m-tolidine, 1,3-bis(4-aminophenoxy)benzene, Examples of the curing agent include 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 4,4'-diaminobenzanilide, 3,4'-diaminodiphenyl ether, bis[4-(3-aminophenoxy)phenyl]sulfone, 3,7-diamino-2,8-dimethyldibenzothiophene sulfone, 5,5'-methylenebis(2-aminobenzoic acid), 1,3'-bis(3-aminophenoxy)benzene, 1,4'-bis(4-aminophenoxy)benzene, etc. Also, these curing agents can be used alone or in combination of two or more.

[0078] Examples of resins having an epoxy group used in the functional group [X] include bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenyl type epoxy resins, cresol novolac type epoxy resins, phenol novolac type epoxy resins, bisphenol A novolac type epoxy resins, alcohol ether type epoxy resins, tetrabromobisphenol A type epoxy resins, naphthalene type epoxy resins, phosphorus-containing epoxy compounds having a structure derived from a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, epoxy resins having a structure derived from a dicyclopentadiene derivative, epoxidized oils and fats such as epoxidized soybean oil, etc. These epoxy resins can be used alone or in combination of two or more.

[0079] Among the epoxy resins, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, cresol novolac type epoxy resin, phenol novolac type epoxy resin, and bisphenol A novolac type epoxy resin are preferred, and naphthalene type epoxy resin is particularly preferred, because they can further improve adhesion. The epoxy group (functional group [X]) of the epoxy resin reacts with the functional group [Y] contained in the insulating resin layer (D) described below to form a covalent bond, thereby improving the adhesion at the interface between the resin layer (C) and the insulating resin layer (D).

[0080] The epoxy equivalent of the epoxy resin is preferably in the range of 100 to 300 g / equivalent, more preferably in the range of 120 to 250 g / equivalent, and even more preferably in the range of 150 to 200 g / equivalent, because this can further improve adhesion.

[0081] In addition, as the resin layer (C), as long as it contains an epoxy group or an amino group, for example, a urethane resin, an acrylic resin, a core-shell type composite resin having a urethane resin as the shell and an acrylic resin as the core, an epoxy resin, a phenoxy resin, an imide resin, an amide resin, a melamine resin, a phenol resin, a urea-formaldehyde resin, a blocked isocyanate polyvinyl alcohol obtained by reacting a blocking agent such as phenol with a polyisocyanate, polyvinylpyrrolidone, etc. may be used in combination.

[0082] The aminotriazine modified novolac resin is a novolac resin in which an aminotriazine ring structure and a phenol structure are bonded via a methylene group. The aminotriazine modified novolac resin can be obtained, for example, by co-condensing an aminotriazine compound such as melamine, benzoguanamine, or acetoguanamine with a phenol compound such as phenol, cresol, butylphenol, bisphenol A, phenylphenol, naphthol, or resorcin and formaldehyde in the presence of a weak alkaline catalyst such as an alkylamine or without a catalyst at about neutral, or by reacting an alkyl ether of an aminotriazine compound such as methyl etherified melamine with the phenol compound.

[0083] The aminotriazine-modified novolak resin is preferably one that does not substantially have a methylol group. The aminotriazine-modified novolak resin may contain a molecule in which only the aminotriazine structure is methylene-bonded, a molecule in which only the phenol structure is methylene-bonded, or the like, which is generated as a by-product during the production of the aminotriazine-modified novolak resin. Furthermore, the aminotriazine-modified novolak resin may contain a small amount of unreacted raw materials.

[0084] Examples of the phenol structure include a phenol residue, a cresol residue, a butylphenol residue, a bisphenol A residue, a phenylphenol residue, a naphthol residue, and a resorcinol residue. The term "residue" used herein means a structure in which at least one hydrogen atom bonded to a carbon atom of an aromatic ring has been removed. For example, in the case of phenol, it means a hydroxyphenyl group.

[0085] Examples of the triazine structure include structures derived from aminotriazine compounds such as melamine, benzoguanamine, and acetoguanamine.

[0086] The phenol structure and the triazine structure can be used alone or in combination of two or more. In addition, the phenol structure is preferably a phenol residue, and the triazine structure is preferably a structure derived from melamine, because these structures can further improve adhesion.

[0087] The hydroxyl value of the aminotriazine modified novolak resin is preferably in the range of 50 to 200 mgKOH / g, more preferably in the range of 80 to 180 mgKOH / g, and even more preferably in the range of 100 to 150 mgKOH / g, since this can further improve adhesion.

[0088] The aminotriazine-modified novolak resins can be used alone or in combination of two or more kinds.

[0089] When an aminotriazine-modified novolak resin is used as the compound having an aminotriazine ring, it is preferable to use an epoxy resin in combination.

[0090] When the resin layer (C) is a layer containing an aminotriazine-modified novolac resin and an epoxy resin, the molar ratio [(x) / (y)] of the phenolic hydroxyl group in the aminotriazine-modified novolac resin to the epoxy group in the epoxy resin is preferably in the range of 0.1 to 5, more preferably in the range of 0.2 to 3, and even more preferably in the range of 0.3 to 2, in order to further improve adhesion.

[0091] In order to promote the reaction between the aminotriazine-modified novolac resin and the epoxy resin, a curing accelerator may be used in combination. Examples of the curing accelerator include amine compounds having a primary, secondary, or tertiary amino group. In addition, any of aliphatic, alicyclic, and aromatic amine compounds can be used as the amine compound. In addition, mercaptans, acid anhydrides, boron acid fluorides, boric acid esters, organic acid hydrazides, Lewis acids, organometallic compounds, onium salts, and cationic compounds can also be used as the curing accelerator.

[0092] It is also preferable to use one containing a phenoxy resin. The resin layer (C) has a function of improving adhesion with the insulating resin layer (D) and the plating underlayer (B) described later. In the present invention, it is preferable to use a phenoxy resin having a weight average molecular weight in the range of 10,000 to 100,000. By using a high molecular weight phenoxy resin for the resin layer (C), the elongation of the polymer is improved, and further, the elastic modulus is improved, so that in the laminate after laminating the surface of the insulating resin layer (D) of the laminate to the support (E) and peeling off the temporary support (A), the resin layer (C) can improve the adhesion between the insulating resin layer (D) and the plating underlayer (B). Furthermore, the use of a high molecular weight phenoxy resin can suppress deterioration such as decomposition of the polymer due to heat during a long-term heat resistance test, so that the adhesion of the metal plating layer (F) can be maintained even after the long-term heat resistance test.

[0093] Phenoxy resin is a polyhydroxy polyether obtained by reacting a divalent phenol compound with epichlorohydrin, or by reacting a divalent epoxy compound with a divalent phenol compound. Examples of divalent phenol compounds include bisphenols. Examples of phenoxy resins include phenoxy resins having a bisphenol A structure (skeleton), phenoxy resins having a bisphenol F structure, phenoxy resins having a bisphenol S structure, phenoxy resins having a bisphenol M structure, phenoxy resins having a bisphenol P structure, and phenoxy resins having a bisphenol Z structure. Other examples include phenoxy resins having a skeleton structure such as a novolac structure, anthracene structure, fluorene structure, dicyclopentadiene structure, norbornene structure, naphthalene structure, biphenyl structure, and adamantane structure. These phenoxy resins may be used alone or in combination of two or more. Among these, those having a bisphenol structure are preferred, and bisphenol A skeleton, bisphenol F skeleton, and bisphenol S skeleton are more preferred. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0094] In the present invention, the weight average molecular weight of the phenoxy resin used is preferably in the range of 10,000 to 100,000. When the molecular weight is 10,000 or more, the plating adhesion after a long-term heat resistance test is high, and when the molecular weight is 100,000 or less, the solubility in organic solvents is improved, and the viscosity of the coating liquid when forming the resin layer (C) becomes appropriate, so that handling becomes good. The preferred weight average molecular weight of the phenoxy resin is 20,000 to 80,000, more preferably 22,000 to 50,000. The weight average molecular weight of the phenoxy resin can be adjusted by the molar ratio of the epoxy resin and the phenol resin and the reaction time in the above reaction. In the present specification, the weight average molecular weight is a value measured by gel permeation chromatography (GPC) described later and converted into standard polystyrene. For the GPC measurement, a high-speed GPC device (HLC-8420GPC, manufactured by Tosoh Corporation) was used as the measurement device, and TSKgel G5000HxL / G4000HxL / G3000HxL / G2000HxL (manufactured by Tosoh Corporation) were used as the columns connected in series, and tetrahydrofuran was used as the eluent, and the measurement was performed using an RI detector. In addition, although a phenoxy resin generally means a high molecular weight epoxy resin, in this specification, the term "epoxy resin" means one having a weight average molecular weight of less than 10,000, and is to be distinguished from the above-mentioned phenoxy resin.

[0095] As the phenoxy resin, commercially available ones may be used. For example, 1256, 4250 (all phenoxy resins containing a bisphenol A skeleton), 4275 (mixed type bisA / bisF), YL6794, YL7213, YL7290, YL7482, YL7553, YX8100 (phenoxy resin containing a bisphenol S skeleton), X6954 (phenoxy resin containing a bisphenol acetophenone skeleton, YX720), all manufactured by Mitsubishi Chemical Corporation, Examples of such phenoxy resins include YP-70 (bisphenol F type phenoxy resin), ZX356-2 (bisphenol A and bisphenol F skeleton-containing phenoxy resin), YPB-40PXM40 (bromine-containing phenoxy resin), ERF-001M30 (phosphorus-containing phenoxy resin), FX-280, FX-293, FX-310 (fluorene skeleton-containing phenoxy resin), and PKHA, PKHB, PKHB+, PKHC, PKHH, PKHJ, and PKFE manufactured by Gabriel Phenoxies.

[0096] In the present invention, the resin layer (C) preferably contains an epoxy resin in combination with the above-mentioned phenoxy resin. By using the phenoxy resin in combination with the epoxy resin, the plating layer adhesion is further improved under normal conditions and after a long-term heat resistance test.

[0097] Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenyl type epoxy resins, cresol novolac type epoxy resins, phenol novolac type epoxy resins, bisphenol A novolac type epoxy resins, alcohol ether type epoxy resins, tetrabromobisphenol A type epoxy resins, naphthalene type epoxy resins, phosphorus-containing epoxy compounds having a structure derived from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, epoxy resins having a structure derived from dicyclopentadiene derivatives, epoxidized oils and fats such as epoxidized soybean oil, etc. These epoxy resins may be used alone or in combination of two or more.

[0098] As the epoxy resin to be used in combination with the phenoxy resin, aromatic epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, cresol novolac type epoxy resin, phenol novolac type epoxy resin, and bisphenol A novolac type epoxy resin are preferred, as they can further improve the adhesion of the metal plating layer (F) described below, and liquid epoxy resins are further preferred, with bisphenol A type epoxy resins being particularly preferred.

[0099] The epoxy equivalent of the epoxy resin used in combination with the phenoxy resin is preferably 100 to 5,000 g / equivalent, more preferably 120 to 2,000 g / equivalent, and even more preferably 120 to 250 g / equivalent, because this can further improve adhesion.

[0100] When the resin layer further contains an epoxy resin in addition to the phenoxy resin, the blending ratio of the phenoxy resin to the epoxy resin is preferably 90:10 to 10:90, and more preferably 85:15 to 15:80, on a mass basis.

[0101] In the present invention, when a phenoxy resin is used for the resin layer (C), the epoxy group at the end of the phenoxy resin reacts with the basic nitrogen atom-containing group contained in the plating underlayer (B), improving the adhesion at the interface between the plating underlayer (B) and the resin layer (C). The phenoxy resin may be used in combination with other resins.

[0102] The resin layer (C) formed by the heating step may have a functional group [X] that remains partially without reacting with the basic nitrogen atom-containing group or the phosphate ester group contained in the compound (b1).

[0103] As described above, the resin layer (C) needs to react the basic nitrogen atom-containing group or phosphate group contained in the plating underlayer (B) with the functional group [X] contained in the resin layer (C) by heating or the like, but the resin layer (C) after drying may be completely cured or semi-cured. Since the method is to form an insulating resin layer (D) on the surface of the resin layer (C) of the laminate described later, and peel off the temporary support (A) of the laminate pasted on the support (E), and thus form a conductive pattern on the insulating resin layer (D), it is preferable that the resin layer (C) is semi-cured in order to ensure adhesion with the insulating resin layer (D).

[0104] The resin layer (C) may be provided on a part or all of the plating underlayer (B) present on the surface of the temporary support layer (A), or on one or both sides of the temporary support (A). For example, when a conductive pattern is to be formed on the surface of the insulating resin layer (D) described later, a temporary support (A) having a resin layer (C) on the entire surface thereof and having the plating underlayer (B) only on the necessary part of the resin layer (C) can be used. Alternatively, the conductive pattern may be one in which the resin layer (C) is provided only on the part of the surface of the temporary support (A) where the plating underlayer (B) is provided.

[0105] The resin layer (C) may be one layer or may be two or more layers. When two or more resin layers (C) are formed, for example, the layer close to the plating base layer improves adhesion with the plating base layer (B), while the resin layer (C) close to the insulating resin layer (D) described later can improve adhesion with the insulating resin layer (D). In addition, the first resin layer (C) close to the plating base layer (C) becomes a layer close to the plating base layer (B) and the metal plating layer (E) described later, and becomes a part close to the copper wiring when a conductive pattern is formed, so that a resin composition of the resin layer (C) can be selected and formed for the purpose of improving insulation reliability.

[0106] In addition, since the coating material for the resin layer (C) is applied to the surface of the plating underlayer (B) formed on the surface of the temporary support (A), it is preferable to mix an organic solvent to obtain a viscosity that is easy to apply. Examples of the organic solvent include toluene, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, isopropyl alcohol, diacetone alcohol, ethylene glycol, and toluene. These solvents can be used alone or in combination of two or more.

[0107] The amount of the organic solvent used is preferably adjusted appropriately depending on the coating method used when coating the plating underlayer (B) and the desired film thickness of the resin layer (C).

[0108] If necessary, known additives such as a film-forming assistant, a leveling agent, a thickener, a water repellent, an antifoaming agent, and an antioxidant may be appropriately added to the coating material for the resin layer (C).

[0109] The resin layer (C) can be formed by coating the resin layer (C) on a part or all of the plating underlayer (B) formed on the surface of the temporary support (A), and removing the organic solvent contained in the coating material for the resin layer (C).

[0110] Examples of the method for applying the coating material for the resin layer (C) include a gravure method, a coating method, a screen method, a roller method, a rotary method, a spray method, a capillary method, and a doctor roll method.

[0111] A typical method for removing the organic solvent contained in the coating layer after applying the coating material of the resin layer (C) to the surface of the plating underlayer (B) formed on the surface of the temporary support (A) is, for example, drying with a dryer to volatilize the organic solvent. The drying temperature must be set within a range that can volatilize the organic solvent used, does not adversely affect the support (A) such as thermal deformation, and reacts the functional group [X] contained in the resin layer (C) with the basic nitrogen atom-containing group or the phosphate ester group contained in the plating underlayer (B) as described above.

[0112] The drying temperature for the resin layer (C) is preferably in the range of 50°C to 400°C, more preferably in the range of 80°C to 340°C, preferably in the range of 120°C to 280°C, and further preferably in the range of 150°C to 200°C.

[0113] The thickness of the resin layer (C) varies depending on the application, but is preferably in a range that further improves the adhesion between the resin layer (C) and the insulating resin layer (D) described below. The thickness of the resin layer (C) is preferably in the range of 10 nm to 30 μm, more preferably in the range of 50 nm to 1 μm, more preferably in the range of 100 nm to 800 nm, and even more preferably in the range of 200 nm to 500 nm.

[0114] The surface of the resin layer (C) may be previously subjected to a surface treatment by a plasma discharge treatment method such as a corona discharge treatment method, a dry treatment method such as an ultraviolet treatment method, or a wet treatment method using water, an acidic or alkaline chemical solution, an organic solvent, or the like, since this can further improve the adhesion between the resin layer (C) and the insulating resin layer (D) in the laminate after the surface of the resin layer (C) of the laminate is formed into an insulating resin layer (D) as described below and the temporary support (A) is peeled off.

[0115] Next, the insulating resin layer (D) will be described. The insulating resin layer (D) needs to be formed on a substrate on which a conductive pattern is to be formed, and therefore needs to be changed depending on the application, such as a printed wiring board, a flexible printed wiring board, a rigid printed wiring board, a package substrate, a ceramic substrate, a glass substrate, a silicon wafer substrate, a metal substrate, an electromagnetic shielding film, or a molded circuit board.

[0116] The insulating resin layer (D) is preferably semi-cured (B stage) because it acts as an interlayer adhesive required when bonding the conductive seed layer and the substrate. For example, if the insulating resin layer (D) is completely cured, problems such as reduced adhesion when bonding to the substrate and reduced embedding ability in the wiring pattern on the substrate may occur.

[0117] The insulating resin layer (D) can be made adhesive by the thermosetting reaction of the insulating resin layer (D) when it is attached to the substrate or wiring pattern by thermocompression. Therefore, it is preferable that the insulating resin layer (D) is in a semi-cured state where the crosslinking reaction has not progressed before lamination. Since the insulating resin layer where the crosslinking reaction has not progressed is soluble in THF solvent, which has excellent solubility, the smaller the THF solution insoluble matter (wt%), the less the crosslinking reaction in the resin has progressed, and the better the adhesion to the substrate or wiring pattern.

[0118] The THF solution insoluble content (wt%) of the insulating resin layer (D) can be calculated by the following method. For example, a coating material for the insulating resin layer (D) is applied to a copper foil support, and after drying, the copper foil is removed by etching with copper chloride or iron chloride to produce a semi-cured resin-only film. The resin-only film is then immersed in a THF solution for 24 hours at room temperature, and the resin-only film that was insoluble in THF is separated using filter paper and its weight is measured. The proportion of the THF insoluble content is then calculated using the following formula: THF insoluble content (wt%) = weight of resin-only film after immersion in THF (g) / weight of resin-only film before immersion in THF (g)

[0119] Therefore, specifically, the THF solution insoluble content of the insulating resin layer (D) is preferably in the range of 1 to 80% by weight, more preferably in the range of 10 to 80% by weight, and further preferably in the range of 20 to 70%.

[0120] The insulating resin layer (D) forms a chemical bond by reacting a functional group [Y] of a compound (d1) present in a coating film formed by coating, drying, etc. on the surface of the resin layer (C) with a functional group [X] of a compound (c1) contained in the resin layer (C).

[0121] The coating film (d), which can be said to be a precursor of the insulating resin layer (D), is formed by applying a composition containing a compound (d1) having a functional group [Y] to the surface of a support, followed by drying, etc. The compound (d1) contained in the coating film (d) has a functional group [Y] that reacts with the compound (c1) having a functional group [X] contained in the resin layer (C).

[0122] Examples of the functional group [Y] that reacts with the functional group [X], which is an epoxy group or an amino group, contained in the resin layer (C) include an epoxy group, a maleimide group, a hydroxy group, a vinylbenzyl group, an acrylate group, a methacrylate group, etc. The functional group [Y] reacts as the functional group [X], and the epoxy group reacts with a carbonyl group or a hydroxy group, and the vinylbenzyl group, the acrylate group, or the methacrylate group reacts with each other, thereby forming a strong insulating resin layer.

[0123] The functional group [Y] is preferably present in a range of 50 mmol / kg to 10,000 mmol / kg, more preferably in a range of 75 mmol / kg to 8,000 mmol / kg, and even more preferably in a range of 100 mmol / kg to 5,000 mmol / kg, relative to the entire insulating resin layer (D), in order to further improve adhesion.

[0124] Examples of the components of the insulating resin layer (D) include epoxy compounds, maleimide compounds, phenol compounds, unsaturated imide compounds, cyanate compounds, isocyanate compounds, benzoxazine compounds, oxetane compounds, amino compounds, unsaturated polyester compounds, allyl compounds, dicyclopentadiene compounds, silicone compounds, triazine compounds, melamine compounds, vinylbenzene compounds, liquid crystal polymers (LCPs), polyether ether ketone (PEEK) compounds, polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), polystyrene compounds (PS), polyphenylene ether (PPE), and other resins modified with functional groups at the ends thereof. These resins may be used alone or in combination of two or more.

[0125] Examples of materials having an epoxy group for the insulating resin layer (D) include preferred ones such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, and epoxy resins having a butadiene structure, more preferred ones are bisphenol A type epoxy resins, bisphenol F type epoxy resins, alicyclic epoxy resins having an ester skeleton, and naphthalene type epoxy resins, further preferred ones are bisphenol A type epoxy resins and bisphenol F type epoxy resins, and from the viewpoint of an excellent balance of physical properties of the cured product, bisphenol A type epoxy resins are particularly preferred. Specific examples of liquid epoxy resins include "HP4032", "HP4032H", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation, "828US", "jER828EL" (bisphenol A type epoxy resin), "jER807" (bisphenol F type epoxy resin), "jER152" (phenol novolac type epoxy resin), and "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "EX-721" (glycidyl ester type) manufactured by Nagase ChemteX Corporation. Preferred are tetrafunctional epoxy resins, "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) and "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation, naphthalene-type tetrafunctional epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, and tetraphenylethane-type epoxy resins, and more preferred are naphthalene-type tetrafunctional epoxy resins, naphthol-type epoxy resins, and biphenyl-type epoxy resins.Specific examples of solid epoxy resins include "HP-4700", "HP-4710" (naphthalene-type tetrafunctional epoxy resin), "N-690" (cresol novolac-type epoxy resin), "N-695" (cresol novolac-type epoxy resin), "HP-7200" (dicyclopentadiene-type epoxy resin), "EXA7311", "EXA7311-G3", "EXA7311-G4", "EXA7311-G4S", and "HP6000" (naphthylene ether-type epoxy resin), and "EPPN-502H" (trisphenol-type epoxy resin), "NC7000L" (naphthol novolac-type epoxy resin), "NC3000H", "NC3000", "NC3000L", and "NC3100" (manufactured by Nippon Kayaku Co., Ltd.). (biphenyl type epoxy resin), "ESN475V" (naphthol type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin (biphenyl type epoxy resin)), "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd., "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd., "jER1010" (solid bisphenol A type epoxy resin) and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd., and the like. These epoxy resins may be used alone or in combination of two or more types.

[0126] The compound having a maleimide group in the insulating resin layer (D) preferably includes, for example, at least one selected from the group consisting of maleimide compounds having one or more (preferably two or more) N-substituted maleimide groups and derivatives thereof. The maleimide compound having one or more N-substituted maleimide groups is not particularly limited, and examples thereof include aromatic maleimide compounds having one N-substituted maleimide group bonded to an aromatic ring, such as N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, and N-benzylmaleimide; 4,4'-diphenylmethane bismaleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1 aromatic bismaleimide compounds having preferably two N-substituted maleimide groups bonded to an aromatic ring, such as 3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, and aromatic bismaleimide containing an indane ring; aromatic polymaleimide compounds having preferably three or more N-substituted maleimide groups bonded to an aromatic ring, such as polyphenylmethane maleimide and biphenyl aralkyl type maleimide; aliphatic maleimide compounds such as N-dodecylmaleimide, N-isopropylmaleimide and N-cyclohexylmaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, and pyrrolidine binder type long chain alkyl bismaleimide. These maleimide compounds may be used alone or in combination of two or more.

[0127] Examples of the phenolic compound having a hydroxyl group in the insulating resin layer (D) include phenolic compounds having 6 to 40 carbon atoms (preferably 6 to 30, more preferably 6 to 23, and even more preferably 6 to 22), and preferred specific examples include phenolic compounds such as hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, and dicyclopentadiene-type diphenol. These phenolic compounds may be used alone or in combination of two or more.

[0128] The compound having a terminal double bond such as a vinylbenzyl group, an acrylate group, or a methacrylate group in the insulating resin layer (D) may be a compound having a phenolic hydroxyl group in the molecule substituted with a reactive functional group, etc. Although the compound having a phenolic hydroxyl group is not particularly limited, polyphenylene ether compounds have excellent heat resistance and dielectric properties, and therefore can be suitably used as a laminate for use in a printed wiring board for high frequency applications.

[0129] The insulating resin layer (D) may be a compound having a structure in which hydrogen atoms of benzene are replaced with a vinylbenzyl group, an acrylate group, or a methacrylate group. In particular, a styrene-based compound, which is a compound having a vinylbenzyl group, has low intramolecular polarity and is excellent in heat resistance and dielectric properties, and therefore can be suitably used as a laminate for use in a printed wiring board for high frequency applications.

[0130] The insulating resin layer (D) contains an inorganic compound (x) in order to prevent dimensional changes due to thermal history during processing when the insulating resin layer (D) is formed on the base material (E) described later by thermocompression bonding and to ensure long-term reliability. This makes it possible to maintain high dimensional stability and long-term reliability.

[0131] The inorganic compound (x) may be in the form of powder, flakes, fibers, or the like.

[0132] The material of the inorganic compound (x) is not particularly limited, and examples thereof include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, spherical silica is preferred as the silica. The inorganic filler may be used alone or in combination of two or more. Commercially available spherical fused silica includes "SO-C2" and "SO-C1" manufactured by Admatechs Co., Ltd.

[0133] The insulating resin layer (D) may be one layer or may be two or more layers. When two or more insulating resin layers (D) are formed, for example, the adhesion with the resin layer (C) is improved, while the insulating resin layer (D) close to the support (E) described later can improve the adhesion with the support (E). In addition, the first insulating resin layer (D) close to the resin layer (C) becomes a layer close to the resin layer (C) and the support (E) described later, and becomes a part close to the copper wiring when a conductive pattern is formed, so that a resin composition of the insulating resin layer (D) can be selected and formed for the purpose of improving insulation reliability.

[0134] In addition, since the coating material for the insulating resin layer (D) is applied to the surface of the resin layer (C) formed on the surface of the plating underlayer (B), it is preferable to mix an organic solvent to obtain a viscosity that is easy to apply. Examples of the organic solvent include toluene, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, isopropyl alcohol, diacetone alcohol, ethylene glycol, and toluene. These solvents can be used alone or in combination of two or more.

[0135] The amount of the organic solvent used is preferably adjusted appropriately depending on the coating method used when coating the insulating resin layer (D) and the desired film thickness of the insulating resin layer (D).

[0136] Furthermore, known additives such as film-forming assistants, leveling agents, thickeners, water repellents, antifoaming agents, and antioxidants may be appropriately added to the coating material for the insulating resin layer (D) as required.

[0137] The insulating resin layer (D) can be formed by applying the insulating resin layer (D) to a part or all of the resin layer (C) formed on the surface of the plating base layer (B) and removing the organic solvent contained in the coating material for the insulating resin layer (D).

[0138] Examples of methods for applying the coating material for the insulating resin layer (D) include inkjet printing, reverse printing, screen printing, offset printing, gravure printing, flexographic printing, pad printing, spin coating, spray coating, bar coating, die coating, slit coating, roll coating, dip coating, rotary coating, capillary coating, small diameter gravure coating, and doctor roll methods.

[0139] A method for removing the organic solvent contained in the coating layer after applying the coating material of the insulating resin layer (D) to the surface of the resin layer (C) on the surface of the plating underlayer (B) formed on the surface of the temporary support (A) is, for example, to dry the coating layer using a dryer to volatilize the organic solvent. The drying temperature must be set within a range that can volatilize the organic solvent used, does not have adverse effects such as thermal deformation on the support (A), and reacts the functional group [Y] contained in the resin layer (D) with the functional group [X] contained in the insulating resin layer (C) as described above.

[0140] The insulating resin layer (D) is in a state where the resin composition has been partially cured to such an extent that the resin composition can be further cured, and is in a semi-cured state (B stage). For example, when the resin composition is heated, the viscosity first gradually decreases, and then the curing starts and the viscosity increases. When the insulating resin layer (D) is in a completely cured state, the conformability of the insulating resin layer (D) decreases when the insulating resin layer (D) is thermocompressed to the substrate (E) described later, so the drying temperature must be set to a temperature range where the insulating resin layer (D) is not completely cured.

[0141] The drying temperature for the insulating resin layer (D) is preferably in the range of 30°C to 400°C, more preferably in the range of 40°C to 200°C, and further preferably in the range of 50°C to 150°C.

[0142] In addition, the resin composition for the insulating resin layer (D) may be used to prepare a varnish-like paint, which may be impregnated into a fibrous substrate, and the semi-cured insulating resin prepreg (D1) may be thermocompressed onto the surface of the resin layer (C) on the surface of the plating base layer (B) formed on the surface of the temporary support (A), thereby forming the insulating resin layer (D).

[0143] Examples of the fibrous base material for the insulating resin layer (D) include glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and linter paper.

[0144] The insulating resin prepreg (D1) can be impregnated into the fibrous base material by immersion, coating, etc., and can be repeatedly impregnated multiple times as necessary. In addition, the impregnation can be repeated using multiple resin compositions with different compositions and concentrations.

[0145] The drying temperature for the insulating resin prepreg (D1) is preferably in the range of 30°C to 400°C, more preferably in the range of 40°C to 200°C, and further preferably in the range of 50°C to 150°C.

[0146] The insulating resin prepreg (D1) can be bonded to the surface of the resin layer (C) on the surface of the plating underlayer (B) formed on the surface of the temporary support (A) by using heat and pressure. Although not particularly limited, for example, a thermal lamination method, a solventless lamination method, an extrusion lamination method, a wet lamination method, a hot roll transfer method, an in-mold transfer method, a pressing method, a vacuum pressing method, a hydraulic transfer method, etc. can be used.

[0147] Regarding the thermocompression bonding conditions, since the insulating resin prepreg (D1) is preferably in the B stage when the insulating resin prepreg (D1) is bonded to the substrate (E) described below, the heating conditions are preferably in the range of 50° C. to 200° C., more preferably in the range of 60° C. to 175° C., and still more preferably in the range of 100° C. to 150° C. The pressure conditions are preferably in the range of 0.05 MPa to 35 MPa, more preferably in the range of 0.3 MPa to 20 MPa, and still more preferably in the range of 0.3 MPa to 20 MPa.

[0148] The thickness of the insulating resin layer (D) varies depending on the application, but is preferably in a range that further improves the adhesion between the insulating resin layer (D) and the support (E) described later, and the thickness of the insulating resin layer (D) is preferably in the range of 1 μm to 1,000 μm, more preferably in the range of 1 μm to 500 μm, and still more preferably in the range of 1 μm to 200 μm.

[0149] The surface of the insulating resin layer (D) may be previously surface-treated, if necessary, by a plasma discharge treatment method such as a corona discharge treatment method, a dry treatment method such as an ultraviolet treatment method, or a wet treatment method using water, an acidic or alkaline chemical solution, an organic solvent, or the like, in order to further improve the adhesion between the insulating resin layer (D) and the support (E) in the laminate after laminating the surface of the insulating resin layer (D) of the laminate to the support (E) and peeling off the temporary support (A), as described below.

[0150] The Tg of the insulating resin layer (D) in the semi-cured form is preferably lower than that of the resin layer (C). When the surface of the insulating resin layer (D) of the transfer laminate is laminated to the support (E) by thermocompression bonding, the insulating resin layer (D) flows out of the plating underlayer (B) or the coating defects of the resin layer (C), and inhibits the adhesion between the metal plating layer (E) and the plating underlayer (B), which will be described later. Therefore, the Tg of the resin layer (C) is made higher than that of the semi-cured insulating resin layer (D), so that the barrier properties can be imparted. Specifically, the peak temperature of tan δ measured using a solid viscoelasticity / dynamic thermomechanical analyzer (DMA) is defined as Tg, and the value of Tg of the semi-cured insulating resin layer (D) is smaller than that of the resin layer (C), and the difference in Tg is preferably in the range of 1°C to 200°C, more preferably in the range of 10 to 150°C, and even more preferably in the range of 30 to 100°C.

[0151] Next, the support (E) will be described. The support (E) serves as a base material for forming a conductive pattern, and therefore needs to be changed depending on the application, such as a printed wiring board, flexible printed wiring board, rigid printed wiring board, package substrate, ceramic substrate, glass substrate, silicon wafer substrate, metal substrate, electromagnetic shielding film, or molded circuit board.

[0152] Examples of materials for the support (E) include polyimide resins, modified polyimide resins (MPI), polyamideimide resins, polyamide resins, polyethylene terephthalate resins, polybutylene terephthalate resins, polyethylene naphthalate resins, polycarbonate resins, acrylonitrile-butadiene-styrene (ABS) resins, polyarylate resins, polyacetal resins, acrylic resins such as poly(methyl meth)acrylate, polyvinylidene fluoride resins, polytetrafluoroethylene resins, polyvinyl chloride resins, polyvinylidene chloride resins, vinyl chloride resins graft-copolymerized with acrylic resins, polyvinyl alcohol resins, polyethylene resins, polypropylene resins, and urethane resins. , cycloolefin resin, polystyrene, liquid crystal polymer (LCP), polyether ether ketone (PEEK) resin, polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), bismaleimide-triazine resin (BT resin), fluororesin composite polyimide resin (film with a fluororesin layer formed on the surface of a polyimide resin), thermoplastic polyimide resin composite polyimide resin (film with a thermoplastic polyimide resin layer formed on the surface of a polyimide resin), cellulose nanofiber, silicon, silicon carbide, gallium nitride, sapphire, ceramics, glass, diamond-like carbon (DLC), alumina, etc.

[0153] In addition, a resin substrate containing a thermosetting resin and an inorganic filler can be suitably used as the support (E). Examples of the thermosetting resin include epoxy resin, phenol resin, unsaturated imide resin, cyanate resin, isocyanate resin, benzoxazine resin, oxetane resin, amino resin, unsaturated polyester resin, allyl resin, dicyclopentadiene resin, silicone resin, triazine resin, melamine resin, liquid crystal polymer (LCP), polyether ether ketone (PEEK) resin, polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), etc. On the other hand, examples of the inorganic filler include silica, alumina, talc, mica, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum borate, borosilicate glass, etc. These thermosetting resins and inorganic fillers can be used alone or in combination of two or more.

[0154] The inorganic filler may be in the form of powder, flakes, fibers, or the like.

[0155] The support (E) may be in the form of a planar flexible material, a rigid material, or a rigid-flexible material. More specifically, the support (E) may be a commercially available material formed into a film, sheet, or plate shape, or may be a material formed into a planar shape from a solution, melt, or dispersion of the above-mentioned resin. The support (E) may be a substrate in which the above-mentioned resin material is formed on a conductive material such as a metal, or a substrate in which the above-mentioned resin material is laminated on a printed wiring board on which a circuit pattern is formed. As a method of lamination, if the support (E) is semi-cured such as a prepreg, it may be attached to a printed wiring board on which a circuit pattern is formed by heat and pressure, and if the support (E) is fully cured, it may be laminated using an adhesive sheet such as a bonding sheet.

[0156] In the case of flexible wiring boards, polyimide resin, modified polyimide resin (MPI), transparent polyimide, polytetrafluoroethylene resin, cycloolefin resin, polystyrene, liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyamide, fluororesin composite polyimide resin (film with a fluororesin layer formed on the surface of polyimide resin, multilayer film with polyimide resin and fluororesin alternately laminated), thermoplastic polyimide resin composite polyimide resin (film with a thermoplastic polyimide resin layer formed on the surface of polyimide resin), etc. can be used.

[0157] When the support (E) is in the form of a film or sheet, the thickness is not particularly limited, but taking into consideration flexibility and bendability, the thickness is usually about 1 to 5,000 μm, more preferably 1 to 500 μm, and even more preferably 1 to 200 μm.

[0158] In the case of rigid wiring boards, composite substrates of glass fiber and epoxy resin (glass epoxy resin, FR-4, FR-5), composite substrate of paper and epoxy resin (FR-3), composite substrate of glass nonwoven fabric and epoxy resin (CEM-3), composite substrate of paper, glass nonwoven fabric and epoxy resin (CEM-1), composite substrate of paper and phenolic resin (paper phenolic resin, FR-1, FR-2), composite substrate of glass fiber and PPE resin (e.g. Panasonic's Megtron 6), bismaleimide triazine resin (BT resin), composite substrate of silica and epoxy resin (e.g. Ajinomoto Co., Inc., Examples of materials that can be used include a build-up film manufactured by Epson Corporation), polyimide, liquid crystal polymer, polyether ether ketone, polyphenylene sulfide, polystyrene, polycarbonate, polyester resin, polypropylene, polyethylene, acrylic resin, urethane resin, cycloolefin polymer, glass, silicon, silicon carbide, gallium nitride, gallium oxide, sapphire, ceramics, alumina ceramic, alumina, glass, diamond-like carbon, aluminum, stainless steel, copper, silver, gold, iron, and nickel.

[0159] Examples of the support (E) include synthetic fibers such as polyester fibers, polyamide fibers, and polyaramid fibers; inorganic fibers such as carbon fibers; and natural fibers such as cellulose nanofibers.

[0160] The surface of the support (E) is preferably smooth in a printed wiring board that requires high-frequency transmission. In the fifth generation mobile communication system (5G) and millimeter wave communication, the frequency of the alternating current is increasing for high-speed communication, and the higher the frequency, the more the skin effect occurs in which the current flows on the surface layer of the copper wiring. If the unevenness of the outermost surface layer of the copper wiring through which the current flows is large, it becomes a resistance and the transmission loss increases. Therefore, the surface of the support (E) is preferably smooth, and the surface roughness (maximum height Sz) measured with a laser microscope is preferably in the range of 0.001 to 30 μm, preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. The surface roughness (maximum height Sz) is measured by the evaluation method described in ISO 25178 and represents the distance from the highest point to the lowest point on the surface.

[0161] Methods for smoothing the support (E) include a method for physically smoothing the surface of the support (E) and a method for smoothing the surface by chemical treatment. Examples of methods for physically smoothing include calendaring, which involves passing the support (E) between two smooth rolls to smooth the surface, cutting, grinding, abrasive polishing, electric discharge machining, laser machining, and water jet machining. Examples of methods for smoothing the surface by chemical treatment include electrolytic polishing and etching polishing.

[0162] In addition, when the support (E) is an uncured or semi-cured thermosetting resin or a thermoplastic resin, a smooth metal foil such as a copper foil or an aluminum foil, or a smooth heat-resistant film such as a polyimide film or a fluororesin film can be used as a smoothing treatment substrate, and the smooth surface can be attached to the surface of the support (E) by thermocompression bonding, and then peeled off to transfer the smooth surface to the surface of the support (E). In particular, when the support (E) is a substrate for a rigid substrate containing a thermosetting resin such as an epoxy resin or a polyphenylene ether resin, glass fiber, or an inorganic filler, the smooth surface of the copper foil can be thermocompressed to the substrate using a press or the like, and then the copper foil can be removed by etching the copper foil with copper chloride or iron chloride to make the substrate surface smooth. The surface roughness of the smoothing treatment substrate affects the surface roughness of the support (E) that is ultimately to be made smooth. Therefore, the surface roughness of the smoothing-treated substrate is preferably smooth, and the surface roughness (maximum height Sz) measured by a laser microscope is preferably in the range of 0.001 to 30 μm, more preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. The surface roughness (maximum height Sz) is measured by the evaluation method described in ISO 25178, and represents the distance from the highest point to the lowest point on the surface.

[0163] In the laminate in which the insulating resin layer (D) of the laminate is laminated to the support (E) and the temporary support (A) of the laminate is peeled off, and then the insulating resin layer (D), the resin layer (C) and the plating underlayer (B) are formed on the surface of the support (E), the surface of the support (E) may be treated to form fine irregularities to a degree that does not impair smoothness, or to introduce functional groups such as hydroxyl groups, carbonyl groups and carboxyl groups, as necessary, in order to further enhance the adhesion between the insulating resin layer (D) and the support (E). For example, methods such as plasma discharge treatment such as corona discharge treatment, dry treatment such as ultraviolet treatment, and wet treatment using water, an aqueous solution of an acid or alkali, or an organic solvent may be mentioned.

[0164] Next, a method for transferring the laminate onto the support (E) will be described. As a transfer method, a method of laminating the surface of the insulating resin layer (D) of the laminate to the support (E) using heat and pressure can be used. Although not particularly limited, for example, a thermal lamination method, a solventless lamination method, an extrusion lamination method, a wet lamination method, a hot roll transfer method, an in-mold transfer method, a pressing method, a vacuum pressing method, a hydraulic transfer method, etc. can be used.

[0165] When the support (E) is a flexible material and is a roll film, it is preferable to use a thermal lamination method, a solventless lamination method, an extrusion lamination method, or a wet lamination method. The thermal lamination method is more preferable because it is particularly easy to process. On the other hand, when the support (E) is a rigid material, it is preferable to use a pressing method or a vacuum pressing method because it is often thermocompressed in sheets.

[0166] Regarding the thermocompression bonding conditions, the heating conditions are preferably in the range of 50° C. to 400° C., more preferably in the range of 80° C. to 350° C., more preferably in the range of 80° C. to 280° C., more preferably in the range of 100° C. to 200° C., and more preferably in the range of 120° C. to 180° C. The pressure conditions are preferably in the range of 0.05 MPa to 35 MPa, more preferably in the range of 0.3 MPa to 20 MPa, and more preferably in the range of 0.3 MPa to 20 MPa.

[0167] In the case of thermal lamination, the processing time for thermocompression bonding is within 1 second because the thermocompression bonding is performed by the linear pressure of the rolls while the film is being transported. On the other hand, in the case of pressing or vacuum pressing, the processing time is preferably within the range of 1 second to 120 minutes, more preferably within the range of 30 seconds to 60 minutes, and more preferably within the range of 30 seconds to 15 minutes, and from the viewpoint of productivity, the processing time is preferably within the range of 1 minute to 5 minutes.

[0168] In addition, when performing thermocompression bonding, air may get between the laminate and the support (E), or gas may be generated from the support (E) or the laminate and accumulate between the laminate and the support (E), lowering the transfer rate. Therefore, it is preferable to perform thermocompression bonding under vacuum using a vacuum press. As for the vacuum conditions, absolute pressure is preferably 100 hPa or less, more preferably 50 hPa or less, and more preferably 13 hPa or less. It is preferable to perform the treatment under the same heating and pressure conditions as described above.

[0169] In addition, the insulating resin layer (D) can be used in place of the support (E) by laminating the resin layer (C) side of a laminate in which the plating base layer (B) and the resin layer (C) are successively formed on the temporary support (A) to the surface of the insulating resin layer (D) and causing the insulating resin layer (D) to semi-cure to fully cure due to the thermal history during lamination.

[0170] By using the insulating resin layer (D) as the support (E) and forming a metal plating layer (F) described later, it is possible to provide the function of a copper-clad laminate used in printed wiring boards, package substrates, etc. without using the support (E), and therefore it can be applied to thin and small printed wiring boards and package substrates without considering the thickness of the support (E).

[0171] Furthermore, by bonding the semi-cured insulating resin layer (D) and the resin layer (C) together by thermocompression, the functional group [Y] contained in the resin layer (D) reacts with the functional group [X] contained in the resin layer (C), thereby providing a laminate with strong adhesion.

[0172] The insulating resin layer (D) is laminated with the resin layer (C) side of the laminate, which is formed by sequentially forming the plating underlayer (B) and the resin layer (C) on the temporary support (A), and the insulating resin layer (D) is semi-cured to completely cured by the thermal history during lamination, so that the insulating resin layer (D) can be used in place of the support (E). A method will now be described.

[0173] The method for bonding the laminate in which the plating base layer (B) and the resin layer (C) are successively formed on the temporary support (A) on the surface of the insulating resin layer (D) is not particularly limited, but for example, a thermal lamination method, a solventless lamination method, an extrusion lamination method, a wet lamination method, a hot roll transfer method, an in-mold transfer method, a pressing method, a vacuum pressing method, a hydraulic transfer method, etc. can be used.

[0174] When the support (E) is a flexible material and is a roll film, it is preferable to use a thermal lamination method, a solventless lamination method, an extrusion lamination method, or a wet lamination method. The thermal lamination method is more preferable because it is particularly easy to process. On the other hand, when the support (E) is a rigid material, it is preferable to use a pressing method or a vacuum pressing method because it is often thermocompressed in sheets.

[0175] Regarding the thermocompression bonding conditions, the heating conditions are preferably in the range of 50° C. to 400° C., more preferably in the range of 80° C. to 350° C., more preferably in the range of 80° C. to 280° C., more preferably in the range of 100° C. to 200° C., and more preferably in the range of 120° C. to 180° C. The pressure conditions are preferably in the range of 0.05 MPa to 35 MPa, more preferably in the range of 0.3 MPa to 20 MPa, and more preferably in the range of 0.3 MPa to 20 MPa.

[0176] In the case of thermal lamination, the processing time for thermocompression bonding is within 1 second because the thermocompression bonding is performed by the linear pressure of the rolls while the film is being transported. On the other hand, in the case of pressing or vacuum pressing, the processing time is preferably within the range of 1 second to 120 minutes, more preferably within the range of 30 seconds to 60 minutes, and more preferably within the range of 30 seconds to 15 minutes, and from the viewpoint of productivity, the processing time is preferably within the range of 1 minute to 5 minutes.

[0177] In addition, when performing thermocompression bonding, air may get between the laminate and the support (E), or gas may be generated from the support (E) or the laminate and accumulate between the laminate and the support (E), lowering the transfer rate. Therefore, it is preferable to perform thermocompression bonding under vacuum using a vacuum press. As for the vacuum conditions, absolute pressure is preferably 100 hPa or less, more preferably 50 hPa or less, and more preferably 13 hPa or less. It is preferable to perform the treatment under the same heating and pressure conditions as described above.

[0178] Next, a method of laminating the surface of the insulating resin layer (D) of the laminate to the support (E) and peeling off the temporary support (A) will be described. The method of peeling off the temporary support (A) is not particularly limited, but when the adhesion between the support (E) and the insulating resin layer (D) is low during the thermocompression bonding (temporary adhesion state), the insulating resin layer (D), the resin layer (C), and the plating underlayer (B) may not be sufficiently transferred to the support (E) and may remain partially on the laminate side, so the direction and speed of peeling off the temporary support (A) when peeling off is important. Specifically, it is preferable to peel off the support (E) in a direction of 90 degrees to 180 degrees, preferably in a range of 120 degrees to 180 degrees, and preferably in a direction of 150 degrees to 180 degrees. When peeling off, it is preferable to peel off the temporary support (A) side at the above-mentioned angle, not the support (E) side. The peeling speed is preferably in the range of 0.01 m / min to 20 m / min, more preferably in the range of 0.05 to 10 m / min, and more preferably in the range of 0.5 to 5 m / min.

[0179] Another method for peeling off the temporary support (A) is peeling off with a chemical solution. For example, when the temporary support (A) is an alkali-soluble polymer film, the temporary support (A) can be peeled off by immersing it in an alkaline aqueous solution. When the temporary support (A) is a metal such as copper or aluminum, the temporary support (A) can be peeled off with an aqueous solution of copper chloride etching solution, iron chloride etching solution, sulfuric acid hydrogen peroxide, or the like.

[0180] Next, the post-treatment of the laminate after laminating the surface of the insulating resin layer (D) of the laminate to the support (E) and then peeling off the temporary support (A) of the laminate will be described. As described above, the resistance of the plating underlayer is reduced, the semi-cured insulating resin layer (D) or the resin layer (C) is completely cured, and the functional group [X] of the compound (c1) contained in the resin layer (C) reacts with the functional group [Y] of the compound (d1) contained in the insulating resin layer (D), and the functional group [X] of the compound (c1) contained in the resin layer (C) reacts with the basic nitrogen atom-containing group or the phosphate ester group of the dispersant (b1) contained in the plating underlayer (B) to form a bond. In addition, in order to further improve the adhesion between the support (E) and the insulating resin layer (D), a heat treatment may be performed. The heat treatment conditions are preferably in the range of 80°C to 400°C, more preferably in the range of 100°C to 350°C, more preferably in the range of 120°C to 325°C, and more preferably in the range of 150°C to 300°C. The heat treatment time is preferably in the range of 1 second to 168 hours, more preferably in the range of 30 seconds to 72 hours, and further preferably in the range of 1 minute to 30 minutes from the viewpoint of productivity.

[0181] In the next step, a metal plating layer (F) or a pattern resist is formed on the surface of the plating underlayer (B), so it is preferable to carry out a cleaning treatment to clean off components that reduce the adhesion of these layers. Examples of components that reduce adhesion include oligomer components that are present in the film and bleed onto the film surface when the temporary support (A) is a resin film, components of the release agent that are partially transferred to the plating underlayer (B) when a release layer is formed on the temporary support (A), and a metal oxide film on the temporary support when the temporary support (A) is made of metal. Examples of the cleaning treatment include oxidative decomposition of organic matter present on the surface of the plating underlayer (B) by heating, plasma discharge treatment such as corona discharge treatment, dry treatment such as ultraviolet treatment, and wet treatment using water, an aqueous solution of an acid or alkali, water containing ozone (ozone nanobubbles), or an organic solvent.

[0182] The metal plating layer (F) constituting the laminate of the present invention is a layer provided for the purpose of forming a highly reliable wiring pattern that can maintain good electrical conductivity for a long period of time without causing breaks or the like, for example, when the laminate is used in a printed wiring board or the like.

[0183] Furthermore, when the plating base layer (B) is formed over the entire surface of the support (E), the metal plating layer (F) is also formed over the entire surface of the support (E); on the other hand, when the plating base layer (B) is present only in a portion of the support (E), the metal plating layer (F) is formed only in the portion of the plating base layer (B).

[0184] The metal plating layer (F) is a layer formed on the plating underlayer (B), and a dry plating method or a wet plating method can be used as a method for forming the metal plating layer (F). Examples of the dry plating method include a metal vapor deposition method and a metal sputtering method. Examples of the wet plating method include an electrolytic plating method and an electroless plating method. It is preferable to use a wet plating method because the metal plating layer (F) can be easily formed. Two or more of these plating methods may be combined. For example, the metal plating layer (F) may be formed by performing electrolytic plating after performing electroless plating. When the plating underlayer (B) has conductivity, it is preferable to perform electrolytic plating directly on the plating underlayer (B) because the cost of plating when forming a conductive pattern can be reduced.

[0185] The electroless plating method is, for example, a method in which an electroless plating solution is brought into contact with a metal constituting the plating underlayer (B), thereby precipitating a metal such as copper contained in the electroless plating solution and forming an electroless plating layer (film) consisting of a metal film.

[0186] The electroless plating solution may contain, for example, a metal such as copper, silver, gold, nickel, chromium, cobalt, or tin, a reducing agent, and a solvent such as an aqueous medium or an organic solvent.

[0187] Examples of the reducing agent include dimethylaminoborane, hypophosphorous acid, sodium hypophosphite, dimethylamineborane, hydrazine, formaldehyde, sodium borohydride, and phenol.

[0188] The electroless plating solution may contain, as necessary, a complexing agent such as a monocarboxylic acid, such as acetic acid or formic acid; a dicarboxylic acid compound, such as malonic acid, succinic acid, adipic acid, maleic acid or fumaric acid; a hydroxycarboxylic acid compound, such as malic acid, lactic acid, glycolic acid, gluconic acid or citric acid; an amino acid compound, such as glycine, alanine, iminodiacetic acid, arginine, aspartic acid or glutamic acid; an aminopolycarboxylic acid compound, such as iminodiacetic acid, nitrilotriacetic acid, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid or diethylenetriaminepentaacetic acid; or a soluble salt (sodium salt, potassium salt, ammonium salt, etc.) of these organic acids, or an amine compound, such as ethylenediamine, diethylenetriamine or triethylenetetramine.

[0189] The electrolytic plating method is a method in which, for example, an electric current is passed through an electrolytic plating solution in contact with a metal constituting the plating base layer (B) or the surface of the electroless plating layer (film) formed by the electroless treatment, thereby precipitating a metal such as copper contained in the electrolytic plating solution onto a conductive material (b2) constituting the plating base layer (B) placed at a cathode or the surface of the electroless plating layer (film) formed by the electroless treatment, thereby forming an electrolytic plating layer (metal film).

[0190] The electrolytic plating solution may contain, for example, a sulfide of a metal such as copper, nickel, chromium, cobalt, or tin, sulfuric acid, and an aqueous medium. Specifically, the electrolytic plating solution may contain copper sulfate, sulfuric acid, and an aqueous medium.

[0191] The electroless plating solution and the electrolytic plating solution are preferably used at a temperature in the range of 20 to 98°C.

[0192] The thickness of the metal plating layer (F) is preferably in the range of 0.01 μm to 100 μm, more preferably in the range of 0.5 μm to 50 μm. The thickness of the metal plating layer (F) can be adjusted by controlling the treatment time, current density, amount of plating additives used, etc. in the plating treatment step for forming the metal plating layer (F).

[0193] Examples of the method for patterning the metal plating layer (F) include photolitho-etching methods such as a subtractive method and a semi-additive method, and a method of plating on the printed pattern of the plating underlayer (B).

[0194] The subtractive method is a method in which an etching resist layer having a shape corresponding to a desired pattern shape is formed on the metal plating layer (F) constituting the laminate of the present invention, which has been previously produced, and then the metal plating layer (F) and the plating underlayer (B) from the portion where the resist has been removed are dissolved and removed with a chemical solution to form a desired pattern. The chemical solution may contain copper chloride, iron chloride, or the like.

[0195] The semi-additive method is a method in which the surface of the insulating resin layer (D) of the laminate is bonded to a support (E), the temporary support (A) of the laminate is peeled off, and then the insulating resin layer (D), the resin layer (C), and the plating underlayer (B) are formed on the surface of the support (E). In the laminate, the plating underlayer (B) is subjected to surface treatment as necessary, and then a plating resist layer having a shape corresponding to a desired pattern is formed on the surface. Then, the metal plating layer (F) is formed by electroless plating, electrolytic plating, or a combination thereof, and then the plating resist layer and the plating underlayer (B) in contact therewith are dissolved and removed in a chemical solution or the like to form a desired pattern. When the plating underlayer (B) is silver, it is preferable to etch it with a chemical agent that selectively etches silver, which will be described later.

[0196] The temporary support layer (A) can be peeled off mechanically, and various commercially available peeling devices can be used. When an alkali-soluble resin is used as the temporary support (A), it can be peeled off by immersing it in an alkaline solution. As the alkaline solution and peeling conditions used for peeling, the peeling solution for pattern resist described later can be appropriately used.

[0197] Next, after peeling off the temporary support (A), a pattern resist of a circuit pattern is formed on the exposed plating underlayer (B).

[0198] In the step of forming the pattern resist, the surface of the plating underlayer (B) may be subjected to a surface treatment such as cleaning treatment with an acidic or alkaline cleaning solution, corona treatment, plasma treatment, UV treatment, gas-phase ozone treatment, liquid-phase ozone treatment, treatment with a surface treatment agent, etc., before the formation of the resist, in order to improve adhesion with the resist layer. These surface treatments may be performed by one method or by a combination of two or more methods.

[0199] Examples of the treatment with the surface treatment agent include a method of treatment using a rust inhibitor consisting of a triazole compound, a silane coupling agent, and an organic acid, as described in JP-A-7-258870; a method of treatment using an organic acid, a benzotriazole rust inhibitor, and a silane coupling agent, as described in JP-A-2000-286546; a method of treatment using a substance having a structure in which a nitrogen-containing heterocycle such as triazole or thiadiazole and a silyl group such as a trimethoxysilyl group or a triethoxysilyl group are bonded via an organic group having a thioether (sulfide) bond, as described in JP-A-2002-363189; A method of treating with a silane compound having a group, a method of treating with an imidazole silane compound obtained by reacting a formyl imidazole compound with an aminopropyl silane compound as described in JP 2015-214743 A, a method of treating with an azole silane compound as described in JP 2016-134454 A, a method of treating with an aromatic compound having an amino group and an aromatic ring in one molecule, a polybasic acid having two or more carboxyl groups, and a solution containing a halide ion as described in JP 2017-203073 A, a method of treating with a surface treatment agent containing a triazole silane compound as described in JP 2018-16865 A, and the like can be used.

[0200] Next, in order to form a metal pattern on the surface, the photosensitive resist of the resist layer is exposed to active light by passing a photomask through it or by using a direct exposure machine. The exposure dose may be appropriately set as necessary. The latent image formed in the photosensitive resist by exposure is removed using a developer to form a pattern resist.

[0201] The developer may be a dilute alkaline aqueous solution of 0.3 to 2 mass % sodium carbonate, potassium carbonate, or the like. A surfactant, an antifoaming agent, or a small amount of an organic solvent to promote development may be added to the dilute alkaline aqueous solution. Development is performed by immersing the exposed substrate in the developer or spraying the developer onto the resist with a spray or the like, and a patterned resist from which the pattern forming portion has been removed can be formed by this development.

[0202] When forming a pattern resist, resist residues such as footing portions generated at the boundary between the cured resist and the substrate and resist deposits remaining on the substrate surface may be removed by a plasma descum treatment or a commercially available resist residue remover.

[0203] The photosensitive resist used in the present invention may be a commercially available resist ink, liquid resist, or dry film resist. It may be appropriately selected depending on the desired pattern resolution, the type of exposure machine used, the type and pH of the chemical solution used in the plating process in the subsequent step, etc.

[0204] Examples of commercially available resist inks include "Plating Resist MA-830" and "Etching Resist X-87" manufactured by Taiyo Ink Mfg. Co., Ltd.; etching resist and plating resist manufactured by NAZDAR; "Etching Resist PLAS FINE PER" series and "Plating Resist PLAS FINE PPR" series manufactured by GOO Chemical Industry Co., Ltd. Examples of electrodeposition resists include "Eagle Series" and "Peper Series" manufactured by Dow Chemical Company. Examples of commercially available dry films include "Photec" series manufactured by Hitachi Chemical Co., Ltd.; "ALPHO" series manufactured by Nikko Materials Co., Ltd.; "Sunfort" series manufactured by Asahi Kasei Corporation; and "Riston" series manufactured by DuPont.

[0205] In order to efficiently manufacture printed wiring boards, it is convenient to use a dry film resist, and in particular, when forming fine circuits, a dry film for semi-additive processing may be used. Examples of commercially available dry films for this purpose include "ALFO LDF500" and "NIT2700" manufactured by Nikko Materials Co., Ltd., "Sunfort UFG-258" manufactured by Asahi Kasei Corporation, "RD Series (RD-2015, 1225)" and "RY Series (RY-5319, 5325)" manufactured by Hitachi Chemical Co., Ltd., and "PlateMaster Series (PM200, 300)" manufactured by DuPont.

[0206] Next, a metal plating layer (F) is formed on the plating underlayer (B) on which the plating resist has been formed. The metal plating layer can be formed by wet plating methods such as electrolytic plating and electroless plating. Two or more of these plating methods may be combined. Since the photosensitive resist peels off when immersed in an alkaline aqueous solution, it is preferable to form the metal plating layer (F) by electrolytic plating.

[0207] The plating base layer (B) is used as a cathode electrode for electrolytic copper plating, and the plating base layer (B) exposed by development as described above is treated by electrolytic copper plating, thereby connecting the through holes of the laminate with copper plating and simultaneously forming a conductive pattern.

[0208] Before forming a conductive pattern by the electrolytic copper plating method, the surface of the plating underlayer (B) may be subjected to a surface treatment, if necessary. Examples of the surface treatment include cleaning treatment with an acidic or alkaline cleaning solution, corona treatment, plasma treatment, UV treatment, gas-phase ozone treatment, liquid-phase ozone treatment, and treatment with a surface treatment agent, under conditions that do not damage the surface of the plating underlayer (B) or the formed resist pattern. These surface treatments can be performed by one method or by a combination of two or more methods.

[0209] In addition, when forming a conductive pattern after the copper plating, annealing may be performed after plating for the purpose of relieving stress of the plating film and improving adhesion. The annealing may be performed before the etching step described below, after the etching step, or before or after the etching step.

[0210] The annealing temperature may be appropriately selected within the range of 40 to 300°C depending on the heat resistance of the substrate used and the purpose of use, but is preferably in the range of 40 to 250°C, and more preferably in the range of 40 to 200°C for the purpose of suppressing oxidative deterioration of the plating film. The annealing time is preferably 10 minutes to 10 days in the temperature range of 40 to 200°C, and about 5 minutes to 10 hours in the case of annealing at a temperature exceeding 200°C. When annealing the plating film, a rust inhibitor may be applied to the plating film surface as appropriate.

[0211] Next, the pattern resist is stripped. After forming a conductive pattern by the plating, the pattern resist formed using the photosensitive resist is stripped, and the plating underlayer (B) of the non-pattern forming portion is removed by an etching solution. The pattern resist may be stripped under the recommended conditions described in the catalog, specifications, etc. of the photosensitive resist used. In addition, as the resist stripper used when stripping the pattern resist, a commercially available resist stripper or a 1.5 to 3 mass % aqueous solution of sodium hydroxide or potassium hydroxide set at 45 to 60°C can be used. The resist can be stripped by immersing the substrate on which the pattern is formed in the stripper or spraying the stripper with a spray or the like.

[0212] In addition, the etching solution used to remove the plating underlayer (B) from the non-pattern forming portion is preferably one that selectively etches only the plating underlayer (B) and does not etch the copper that forms the metal plating layer (F). When silver is used as the plating underlayer (B), an example of such an etching solution is a mixture of carboxylic acid and hydrogen peroxide.

[0213] Examples of the carboxylic acid include acetic acid, citric acid, formic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, oxalic acid, malonic acid, succinic acid, benzoic acid, salicylic acid, phthalic acid, isophthalic acid, terephthalic acid, gallic acid, mellitic acid, cinnamic acid, pyruvic acid, lactic acid, malic acid, citric acid, fumaric acid, maleic acid, aconitic acid, glutaric acid, adipic acid, and amino acids. These carboxylic acids can be used alone or in combination of two or more. Among these carboxylic acids, it is preferable to mainly use acetic acid or citric acid because they are easy to manufacture and handle as an etching solution.

[0214] When a mixture of carboxylic acid and hydrogen peroxide is used as an etching solution, it is believed that hydrogen peroxide reacts with carboxylic acid to generate percarboxylic acid (peroxycarboxylic acid). It is presumed that the generated percarboxylic acid preferentially dissolves silver constituting the plating underlayer (B) while suppressing dissolution of copper constituting the conductive pattern.

[0215] The mixing ratio of the mixture of the carboxylic acid and hydrogen peroxide is preferably in the range of 2 to 100 moles of hydrogen peroxide, more preferably 2 to 50 moles of hydrogen peroxide, per mole of carboxylic acid, since this can suppress dissolution of the copper conductive pattern.

[0216] The mixture of carboxylic acid and hydrogen peroxide is preferably an aqueous solution diluted with water. The content of the mixture of carboxylic acid and hydrogen peroxide in the aqueous solution is preferably in the range of 2 to 65 mass%, more preferably in the range of 2 to 30 mass%, since this can suppress the effect of a temperature rise of the etching solution.

[0217] The water used for the dilution is preferably water from which ionic substances and impurities have been removed, such as ion-exchanged water, pure water, or ultrapure water.

[0218] The etching solution may further contain a protective agent for protecting the copper conductive pattern and suppressing dissolution. As the protective agent, an azole compound is preferably used.

[0219] Examples of the azole compound include imidazole, pyrazole, triazole, tetrazole, oxazole, thiazole, selenazole, oxadiazole, thiadiazole, oxatriazole, and thiatriazole.

[0220] Specific examples of the azole compound include 2-methylbenzimidazole, aminotriazole, 1,2,3-benzotriazole, 4-aminobenzotriazole, 1-bisaminomethylbenzotriazole, aminotetrazole, phenyltetrazole, 2-phenylthiazole, benzothiazole, etc. These azole compounds can be used alone or in combination of two or more.

[0221] The concentration of the azole compound in the etching solution is preferably in the range of 0.001 to 2% by mass, and more preferably in the range of 0.01 to 0.2% by mass.

[0222] In addition, it is preferable to add polyalkylene glycol as a protective agent to the etching solution, since this can suppress dissolution of the copper conductive pattern.

[0223] Examples of the polyalkylene glycol include water-soluble polymers such as polyethylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene block copolymers. Among these, polyethylene glycol is preferred. The number average molecular weight of the polyalkylene glycol is preferably in the range of 200 to 20,000.

[0224] The concentration of the polyalkylene glycol in the etching solution is preferably in the range of 0.001 to 2% by mass, and more preferably in the range of 0.01 to 1% by mass.

[0225] In order to suppress pH fluctuations, additives such as sodium salts, potassium salts, and ammonium salts of organic acids may be added to the etching solution as necessary.

[0226] The plating underlayer (B) in the non-pattern-forming portion can be removed by forming the conductive pattern, and then immersing the substrate from which the pattern resist formed using the photosensitive resist has been peeled off in the etching solution, or by spraying the etching solution onto the substrate with a spray or the like.

[0227] When removing the plating underlayer (B) of the non-pattern forming portion using an etching apparatus, for example, all components of the etching solution may be prepared to have a predetermined composition and then supplied to the etching apparatus, or each component of the etching solution may be supplied separately to the etching apparatus and mixed within the apparatus to prepare the predetermined composition.

[0228] The etching solution is preferably used within a temperature range of 10 to 35°C. In particular, when an etching solution containing hydrogen peroxide is used, it is preferably used within a temperature range of 30°C or less, since this can suppress decomposition of hydrogen peroxide.

[0229] After removing the plating underlayer (B) with the etching solution, a cleaning operation may be performed in addition to rinsing with water in order to prevent the silver component dissolved in the etching solution from adhering to and remaining on the printed wiring board. For the cleaning operation, it is preferable to use a cleaning solution that dissolves silver oxide, silver sulfide, and silver chloride but hardly dissolves silver. Specifically, it is preferable to use an aqueous solution containing thiosulfate or tris(3-hydroxyalkyl)phosphine, or an aqueous solution containing mercaptocarboxylic acid or a salt thereof as the cleaning chemical.

[0230] Examples of the thiosulfates include ammonium thiosulfate, sodium thiosulfate, potassium thiosulfate, etc. Examples of the tris(3-hydroxyalkyl)phosphines include tris(3-hydroxymethyl)phosphine, tris(3-hydroxyethyl)phosphine, tris(3-hydroxypropyl)phosphine, etc. These thiosulfates or tris(3-hydroxyalkyl)phosphines can be used alone or in combination of two or more.

[0231] When using an aqueous solution containing a thiosulfate, the concentration may be appropriately set depending on the process time, the characteristics of the cleaning device used, etc., but is preferably in the range of 0.1 to 40 mass %, and more preferably in the range of 1 to 30 mass % from the viewpoints of cleaning efficiency and stability of the chemical solution during continuous use.

[0232] When an aqueous solution containing tris(3-hydroxyalkyl)phosphine is used, its concentration may be appropriately set depending on the process time, the characteristics of the cleaning device used, etc., but is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 1 to 40 mass % from the viewpoints of cleaning efficiency and stability of the chemical solution during continuous use.

[0233] Examples of the mercaptocarboxylic acid include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, N-acetylcysteine, etc. Examples of the salt of the mercaptocarboxylic acid include alkali metal salts, ammonium salts, amine salts, etc.

[0234] When an aqueous solution of mercaptocarboxylic acid or a salt thereof is used, the concentration is preferably in the range of 0.1 to 20% by mass, and more preferably in the range of 0.5 to 15% by mass from the viewpoints of cleaning efficiency and process costs in the case of treating a large amount.

[0235] Examples of the method for carrying out the above-mentioned cleaning operation include a method of immersing the printed wiring board obtained by etching away the plating underlayer (B) of the non-pattern forming portion in the cleaning solution, a method of spraying the cleaning solution onto the printed wiring board with a spray, etc. The temperature of the cleaning solution can be set at room temperature (25°C), but since the cleaning process can be carried out stably without being affected by the outside air temperature, it may be set at a temperature of, for example, 30°C.

[0236] Moreover, the step of removing the plating underlayer (B) from the non-pattern-forming portion with an etching solution and the washing operation can be repeated as necessary.

[0237] As described above, the printed wiring board of the present invention may be further washed, if necessary, for the purpose of further improving the insulation of the non-pattern-forming portion after the plating underlayer (B) of the non-pattern-forming portion is removed with the etching solution. For this washing operation, for example, an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of potassium hydroxide or sodium hydroxide can be used.

[0238] The cleaning using the alkaline permanganic acid solution includes a method of immersing the printed wiring board obtained by the above method in an alkaline permanganic acid solution set at 20 to 60°C, a method of spraying the alkaline permanganic acid solution onto the printed wiring board with a spray or the like, and the like. The printed wiring board may be treated by contacting it with a water-soluble organic solvent having an alcoholic hydroxyl group before cleaning in order to improve the wettability of the alkaline permanganic acid solution to the substrate surface and improve the cleaning efficiency. Examples of the organic solvent include methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and the like. These organic solvents can be used alone or in combination of two or more kinds.

[0239] The concentration of the alkaline permanganate solution may be appropriately selected as necessary, but is preferably one in which 0.1 to 10 parts by mass of potassium permanganate or sodium permanganate is dissolved in 100 parts by mass of a 0.1 to 10% by mass aqueous solution of potassium hydroxide or sodium hydroxide, and from the viewpoint of cleaning efficiency, more preferably one in which 1 to 6 parts by mass of potassium permanganate or sodium permanganate is dissolved in 100 parts by mass of a 1 to 6% by mass aqueous solution of potassium hydroxide or sodium hydroxide.

[0240] When cleaning with the alkaline permanganate solution, it is preferable to treat the cleaned printed wiring board with a solution having a neutralizing or reducing effect after cleaning with the alkaline permanganate solution. Examples of the solution having a neutralizing or reducing effect include an aqueous solution containing 0.5 to 15 mass % dilute sulfuric acid or an organic acid. Examples of the organic acid include formic acid, acetic acid, oxalic acid, citric acid, ascorbic acid, and methionine.

[0241] The above-mentioned cleaning with the alkaline permanganate solution may be carried out after cleaning for the purpose of preventing the silver components dissolved in the etching solution from adhering to and remaining on the printed wiring board, or, instead of cleaning, only cleaning with the alkaline permanganate solution may be carried out for the purpose of preventing the silver components dissolved in the etching solution from adhering to and remaining on the printed wiring board.

[0242] Furthermore, a printed wiring board obtained using the laminate for printed wiring board of the present invention may be appropriately and optionally subjected to lamination of a coverlay film on the circuit pattern, formation of a solder resist layer, and nickel / gold plating, nickel / palladium / gold plating, or palladium / gold plating as a final surface treatment of the circuit pattern.

[0243] The laminate of the present invention obtained by the above method is different from conventional transfer laminates in that a semi-cured insulating resin layer is formed on a resin layer, and functional groups of the resin layer and the insulating resin layer are reacted with each other, and the laminate has excellent wiring embedding performance, adhesion, and uniform film quality, and can be suitably used as electronic components such as printed wiring boards, rigid printed wiring boards, flexible printed wiring boards, package substrates, ceramic substrates, glass substrates, silicon wafer substrates, metal substrates, conductive films for touch panels, metal meshes for touch panels, organic solar cells, organic EL elements, organic transistors, RFID such as non-contact IC cards, electromagnetic wave shields, LED lighting substrates, and digital signage. In particular, it is optimal for rigid printed wiring boards and flexible printed wiring boards. EXAMPLES

[0244] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples in any way.

[0245] [Preparation Example 1: Preparation of coating solution (1) for forming plating underlayer (B)] Under a nitrogen atmosphere, a solution of p-toluenesulfonic acid chloride in chloroform (30 ml) containing 9.6 parts by mass was added dropwise to a mixture containing 20 parts by mass of methoxypolyethylene glycol (number average molecular weight 2,000), 8.0 parts by mass of pyridine, and 20 ml of chloroform while stirring on ice for 30 minutes, and the mixture was then stirred for 4 hours at a bath temperature of 40°C and mixed with 50 ml of chloroform. The obtained product was then washed with 100 ml of a 5 mass% aqueous hydrochloric acid solution, then washed with 100 ml of a saturated aqueous sodium hydrogencarbonate solution, and then washed with 100 ml of a saturated saline solution, and then dried over anhydrous magnesium sulfate, filtered, concentrated under reduced pressure, washed several times with hexane, filtered, and dried under reduced pressure at 80°C to obtain a methoxypolyethylene glycol having a p-toluenesulfonyloxy group.

[0246] 5.39 parts by mass of methoxypolyethylene glycol having a p-toluenesulfonyloxy group, 20 parts by mass of polyethyleneimine (manufactured by Aldrich, molecular weight 25,000), 0.07 parts by mass of potassium carbonate, and 100 ml of N,N-dimethylacetamide were mixed and stirred at 100° C. for 6 hours under a nitrogen atmosphere. Next, 300 ml of a mixed solution of ethyl acetate and hexane (volume ratio of ethyl acetate / hexane = 1 / 2) was added, and the mixture was stirred vigorously at room temperature, after which the product solid was filtered. The solid was washed with 100 ml of a mixed solution of ethyl acetate and hexane (volume ratio of ethyl acetate / hexane = 1 / 2), and then dried under reduced pressure to obtain a compound in which polyethylene glycol was bound to polyethyleneimine.

[0247] 138.8 parts by mass of an aqueous solution containing 0.592 parts by mass of the compound in which polyethylene glycol is bound to polyethyleneimine obtained was mixed with 10 parts by mass of silver oxide, and the mixture was stirred for 30 minutes at 25° C. Then, 46 parts by mass of dimethylethanolamine was gradually added with stirring, and the mixture was stirred for 30 minutes at 25° C. Next, 15.2 parts by mass of a 10% by mass aqueous ascorbic acid solution was gradually added with stirring, and stirring was continued for 20 hours to obtain a silver dispersion.

[0248] A mixed solvent of 200 ml of isopropyl alcohol and 200 ml of hexane was added to the obtained silver dispersion and stirred for 2 minutes, and then centrifugal concentration was performed at 3000 rpm for 5 minutes. After removing the supernatant, a mixed solvent of 50 ml of isopropyl alcohol and 50 ml of hexane was added to the precipitate and stirred for 2 minutes, and then centrifugal concentration was performed for 10 minutes at 2000 rpm. After removing the supernatant, 20 parts by mass of water was further added to the precipitate and stirred for 2 minutes to remove the organic solvent under reduced pressure. After adding 10 parts by mass of water and stirring and dispersing, the dispersion was left in a freezer at -40 ° C for 1 day and night to freeze, and this was treated with a freeze dryer (FDU-2200 manufactured by Tokyo Rikakikai Co., Ltd.) for 24 hours to obtain silver particles containing a dispersant having a basic nitrogen atom-containing group consisting of flake-shaped lumps with a gray-green metallic luster.

[0249] The obtained powder of silver particles containing a dispersant having a basic nitrogen atom-containing group was dispersed in a mixed solvent of 45 parts by mass of ethanol and 55 parts by mass of ion-exchanged water to prepare a 5% by mass coating solution (1) for forming a plating underlayer (B). The proportion of the dispersant was calculated from the ash content after heating the obtained silver particles in an electric furnace at 500°C for 1 hour, and it was confirmed that the proportion was 5% by mass relative to 100% by mass of silver solids.

[0250] [Preparation Example 2: Preparation of Coating Fluid (1) for Forming Resin Layer (C)] 60 parts by mass of phenoxy resin 4250 (Mitsubishi Chemical Corporation bisphenol A / bisphenol F mixed type, molecular weight 60,000, solid content 100 mass%), 33 parts by mass of aminotriazine novolac resin (DIC Corporation "Phenolite LA-7052", solid content 60 mass%), 17 parts by mass of epoxy resin (DIC Corporation "EPICLON EXA-830CRP"; bisphenol F type epoxy resin, epoxy group equivalent 162 g / equivalent), 3 parts by mass of trimellitic anhydride, 16 parts by mass of "DPE" manufactured by Seika Corporation as a curing agent, and 0.5 parts by mass of "TBZ" manufactured by Shikoku Kasei Co., Ltd. as a curing catalyst were mixed, diluted with cyclohexanone so that the non-volatile content was 2 mass%, and mixed uniformly to obtain a coating liquid (1) for forming the resin layer (C).

[0251] [Preparation Example 3: Preparation of Coating Fluid (2) for Forming Resin Layer (C)] In a nitrogen-substituted vessel equipped with a thermometer, a nitrogen gas inlet tube, and a stirrer, 100 parts by mass of polyester polyol (a polyester polyol obtained by reacting 1,4-cyclohexanedimethanol, neopentyl glycol, and adipic acid), 17.6 parts by mass of 2,2-dimethylolpropionic acid, 21.7 parts by mass of 1,4-cyclohexanedimethanol, and 106.2 parts by mass of dicyclohexylmethane-4,4'-diisocyanate were reacted in a mixed solvent of 178 parts by mass of methyl ethyl ketone to obtain a urethane prepolymer solution having isocyanate groups at its terminals.

[0252] Next, 13.3 parts by mass of triethylamine was added to the urethane prepolymer solution to neutralize the carboxyl groups of the urethane prepolymer, and 380 parts by mass of water was further added and thoroughly stirred to obtain an aqueous dispersion of the urethane prepolymer.

[0253] To the aqueous dispersion of the urethane prepolymer obtained above, 8.8 parts by mass of a 25% by mass ethylenediamine aqueous solution was added and stirred to extend the chain of the urethane prepolymer. Then, by aging and desolvation, an aqueous dispersion of a urethane resin (non-volatile content 30% by mass) was obtained. The weight average molecular weight of the urethane resin was 53,000.

[0254] Next, 140 parts by mass of deionized water and 100 parts by mass of the aqueous dispersion of the urethane resin obtained above were placed in a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, a dropping funnel for dropping a monomer mixture, and a dropping funnel for dropping a polymerization catalyst, and the temperature was raised to 80° C. while blowing in nitrogen. Thereafter, while stirring, a monomer mixture consisting of 60 parts by mass of methyl methacrylate, 30 parts by mass of n-butyl acrylate, and 10 parts by mass of n-butoxymethylacrylamide, and 20 parts by mass of a 0.5% by mass aqueous ammonium persulfate solution were dropped from separate dropping funnels over a period of 120 minutes while maintaining the temperature inside the reaction vessel at 80° C.

[0255] After the dropwise addition was completed, the mixture was stirred at the same temperature for an additional 60 minutes, and then the temperature inside the reaction vessel was cooled to 40°C. The mixture was diluted with deionized water so that the non-volatile content became 2% by mass, and then filtered through a 200-mesh filter cloth to obtain coating solution (2) for forming resin layer (C), which is a core-shell type composite resin having the urethane resin as the shell layer and a vinyl resin made from raw materials such as methyl methacrylate as the core layer.

[0256] <Preparation Example 4: Preparation of coating solution (1) for forming insulating resin layer (D)> 3 parts by mass of bisphenol type epoxy resin ("ZX059" manufactured by Nippon Steel Chemical Co., Ltd., bisphenol A type: bisphenol F type = 1: 1 mixture, epoxy equivalent of about 169), 3 parts by mass of naphthalene type epoxy resin ("HP-4032D" manufactured by DIC Corporation, epoxy equivalent of about 144), 12 parts by mass of crystalline bifunctional epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 185), 9 parts by mass of dicyclopentadiene type epoxy resin ("HP7200H" manufactured by DIC Corporation, epoxy equivalent of about 275), and 10 parts by mass of phenoxy resin ("YX7200B35" manufactured by Mitsubishi Chemical Corporation, MEK solution with solid content of 35% by mass) were dissolved by heating in 30 parts by mass of solvent naphtha while stirring. After cooling to room temperature, 40 parts by mass of an active ester compound (DIC Corporation's "HPC-8000-65T", a toluene solution with a non-volatile content of 65% by mass and an active group equivalent of approximately 223), 3 parts by mass of a curing accelerator (4-dimethylaminopyridine, an MEK solution with a solid content of 5% by mass), and spherical silica (average particle size 0.25 μm, Admatechs Corporation's "SO-C1", carbon amount per unit surface area 0.36 mg / m) surface-treated with a phenylaminosilane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM573"). 2 275 parts by mass of the mixture was diluted with toluene to a non-volatile content of 60% by mass, and the mixture was mixed uniformly to obtain a coating liquid for forming an insulating resin layer (D).

[0257] <Preparation Example 5: Preparation of Coating Solution (2) for Forming Insulating Resin Layer (D)> 70 parts by mass of a terminal methacrylate modified polyphenylene ether resin (SABIC Innovative Plastics, "SA9000"), 30 parts by mass of triallyl isocyanurate (Nippon Kasei Kabushiki Kaisha, "TAIC") as a crosslinking curing agent, 2 parts by mass of a phosphate ester compound (Daihachi Chemical Industry Co., Ltd., "PX-200"), 17 parts by mass of a phosphinate compound (Clariant Japan Co., Ltd., "Exolit OP-935"), 2 parts by mass of a reaction initiator (NOF Corporation, "1,3-bis(butylperoxyisopropyl)benzene"), and 275 parts by mass of an inorganic filler silica (Admatechs Co., Ltd., SO-C1) were diluted with toluene to a non-volatile content of 60% by mass and mixed uniformly to obtain a coating liquid (2) for forming a resin layer (D).

[0258] <Preparation Example 6: Preparation of Transfer Laminate (1)> The coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the surface of the release layer of the release film ("TN-200" manufactured by Toyobo Co., Ltd., a release PET film; thickness 38 μm) using a small desktop coater ("K Printing Profer" manufactured by RK Print Coat Instruments Co., Ltd.) and dried at 150 ° C. for 5 minutes to coat a silver layer corresponding to the plating underlayer (B) to a thickness of 0.1 μm after drying. The plating underlayer (B) on the release film was analyzed with a glow discharge optical emission analyzer, and the signal intensity of the carbon atom present at the interface between the air and the plating underlayer (B) was 0.89, and the signal intensity of the carbon atom present at the interface between the plating underlayer (B) and the release film was 0.43. Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C. for 3 minutes to coat the layer corresponding to the resin layer (C) so that the thickness after drying was 0.3 μm. Thereafter, the coating liquid (1) for forming the resin layer (D) obtained in Preparation Example 4 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 80 ° C. for 4 minutes to coat the layer corresponding to the insulating resin layer (D) so that the thickness after drying was 50 μm (insulating resin layer (D) THF insoluble content: 1%). A plating underlayer (B), a resin layer (C) and an insulating resin layer (D) were formed on the surface of the release film corresponding to the temporary support (A), and a transfer laminate (1) was obtained.

[0259] <Preparation Example 7: Preparation of Transfer Laminate (2)> The coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the surface of the release film ("TN-200" manufactured by Toyobo Co., Ltd., a release PET film; thickness 38 μm) on which the release layer was formed, using a small desktop coater ("K Printing Profer" manufactured by RK Print Coat Instruments Co., Ltd.), and dried at 150 ° C. for 5 minutes to coat the silver layer corresponding to the plating underlayer (B) to a thickness of 0.05 μm after drying. Furthermore, the coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the surface of the silver layer using a small desktop coater ("K Printing Profer" manufactured by RK Print Coat Instruments Co., Ltd.), and dried at 150 ° C. for 5 minutes to coat the silver layer corresponding to the plating underlayer (B) to a thickness of 0.05 μm after drying. The total thickness of the silver layer was 0.1 μm. When the plating base layer (B) on the release film was analyzed using a glow discharge optical emission spectrometer, the signal intensity of the carbon atoms present at the interface between the air and the plating base layer (B) was 0.89, and the signal intensity of the carbon atoms present at the interface between the plating base layer (B) and the release film was 0.43. Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C. for 3 minutes to coat the layer corresponding to the resin layer (C) so that the thickness after drying was 0.3 μm. Thereafter, the coating liquid (2) for forming the resin layer (D) obtained in Preparation Example 5 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 80 ° C. for 4 minutes to coat the layer corresponding to the insulating resin layer (D) so that the thickness after drying was 50 μm (insulating resin layer (D) THF insoluble content: 3%). A plating underlayer (B), a resin layer (C), and an insulating resin layer (D) were formed on the surface of the release film corresponding to the temporary support (A), to obtain a transfer laminate (2).

[0260] <Preparation Example 8: Preparation of transfer laminate (3)> A transfer laminate (3) was obtained in the same manner as in Preparation Example 6, except that the coating liquid (2) for forming the resin layer (C) was used instead of the coating liquid (1) for forming the resin layer (C) of the laminate (1).

[0261] <Preparation Example 9: Preparation of Transfer Laminate (4)> A transfer laminate (4) was obtained in the same manner as in Preparation Example 7, except that the coating liquid (2) for forming the resin layer (C) was used instead of the coating liquid (1) for forming the resin layer (C) of the laminate (2).

[0262] <Preparation Example 10: Preparation of transfer laminate (5)> Instead of the release film of the laminate (1), the glossy side (non-roughened side) of copper foil (F2-WS copper foil manufactured by Furukawa Electric Co., Ltd.; thickness 18 μm) was used, and a transfer laminate (5) was obtained in the same manner as in Preparation Example 6.

[0263] <Preparation Example 11: Preparation of transfer laminate (6)> The coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the shiny side (non-roughened side) of a copper foil (F2-WS copper foil manufactured by Furukawa Electric Co., Ltd.; thickness 18 μm) using a small desktop coater (RK Print Coat Instruments Co., Ltd.'s "K Printing Profer") and dried at 150° C. for 5 minutes to coat a silver layer corresponding to the plating underlayer (B) to a thickness of 0.1 μm after drying. The plating underlayer (B) on the copper foil was analyzed with a glow discharge optical emission analyzer, and the signal intensity of the carbon atoms present at the interface between the air and the plating underlayer (B) was 0.89, and the signal intensity of the carbon atoms present at the interface between the plating underlayer (B) and the release film was 0.43. Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C for 3 minutes, so that the layer corresponding to the resin layer (C) was coated so that the thickness after drying was 0.3 μm. Thereafter, the coating liquid (1) for forming the insulating resin layer (D) was used to impregnate a glass cloth (#7628 type, E glass, manufactured by Nitto Boseki Co., Ltd.), and the prepreg (insulating resin layer (D) prepreg THF insoluble content: 75%) that had been heated and dried at 150 ° C for 4 minutes was bonded to the prepreg at 120 ° C for 10 minutes using a hand press (Toyo Seiki Seisakusho's "Mini Test Press"). A plating underlayer (B), a resin layer (C), and an insulating resin layer (D) were formed on the surface of the release film corresponding to the temporary support (A), to obtain a transfer laminate (6).

[0264] <Preparation Example 12: Preparation of transfer laminate (7)> The coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the shiny side (non-roughened side) of a copper foil (F2-WS copper foil manufactured by Furukawa Electric Co., Ltd.; thickness 18 μm) using a small desktop coater (RK Print Coat Instruments Co., Ltd.'s "K Printing Profer") and dried at 150° C. for 5 minutes to coat a silver layer corresponding to the plating underlayer (B) to a thickness of 0.1 μm after drying. The plating underlayer (B) on the copper foil was analyzed with a glow discharge optical emission analyzer, and the signal intensity of the carbon atoms present at the interface between the air and the plating underlayer (B) was 0.89, and the signal intensity of the carbon atoms present at the interface between the plating underlayer (B) and the release film was 0.43. Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C for 3 minutes, so that the layer corresponding to the resin layer (C) was coated so that the thickness after drying was 0.3 μm. Thereafter, the coating liquid (2) for forming the insulating resin layer (D) was used to impregnate a glass cloth (#7628 type, E glass, manufactured by Nitto Boseki Co., Ltd.), and the prepreg (insulating resin layer (D) prepreg THF insoluble content: 80%) that had been heated and dried at 150 ° C for 4 minutes was bonded to the prepreg at 120 ° C for 10 minutes using a hand press (Toyo Seiki Seisakusho's "Mini Test Press"). A plating underlayer (B), a resin layer (C), and an insulating resin layer (D) were formed on the surface of the release film corresponding to the temporary support (A), to obtain a transfer laminate (7).

[0265] <Preparation Example 13: Preparation of transfer laminate (8)> The coating solution (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to the shiny side (non-roughened side) of a copper foil (F2-WS copper foil manufactured by Furukawa Electric Co., Ltd.; thickness 18 μm) using a small desktop coater (RK Print Coat Instruments Co., Ltd.'s "K Printing Profer") and dried at 150° C. for 5 minutes to coat a silver layer corresponding to the plating underlayer (B) to a thickness of 0.1 μm after drying. The plating underlayer (B) on the copper foil was analyzed with a glow discharge optical emission analyzer, and the signal intensity of the carbon atoms present at the interface between the air and the plating underlayer (B) was 0.89, and the signal intensity of the carbon atoms present at the interface between the plating underlayer (B) and the release film was 0.43. Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied using a small desktop coater (RK Printing Profer, manufactured by RK Print Coat Instruments Co., Ltd.) and dried at 180°C for 3 minutes to coat a layer corresponding to the resin layer (C) so that the thickness after drying was 0.3 μm, thereby obtaining a transfer laminate (8).

[0266] Example 1 Corona treatment (Haruka Electric Co., Ltd.'s "Corona Surface Modification Evaluation Device TEC-4AX", electrode-substrate distance 0.5 mm, 100 W) was performed on both sides of a polyimide film (Toray DuPont Co., Ltd.'s Kapton 150EN-A). Thereafter, the surface of the transfer laminate (1) obtained in Preparation Example 6 on which the insulating resin layer (D) was formed was attached to both sides of the polyimide film, and the laminate was thermocompressed using a laminator (Tester Sangyo Co., Ltd.'s "Small Tabletop Test Laminator") under lamination conditions of roll material metal-metal, roll temperature 160°C, air input pressure 0.4 MPa, and roll speed: 1 m / min. Next, the release film of the laminate (1) thermocompressed on both sides of the polyimide film was peeled off, forming the insulating resin layer (D), the resin layer (C), and the plating underlayer (B) on both sides of the polyimide film. The surface resistance of the plating underlayer (B) was 20 Ω / □ on both the front and back sides. After drying at 250°C for 5 minutes, the surface resistance of the plating underlayer (B) was 1 Ω / □ on both the front and back sides.

[0267] Thereafter, the above-obtained plating underlayer (B) was set as the cathode side, and phosphorus-containing copper was set as the anode side, and electroplating was performed at a current density of 2 A / dm using an electrolytic plating solution containing copper sulfate. 2 For 27 minutes, electrolytic plating was performed at 400 K for 27 minutes to form a copper plating layer (12 μm thick) corresponding to the metal plating layer (F) on the plating underlayer (B). The electrolytic plating solution used was 70 g / L copper sulfate, 200 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additive (Top Lucina SF-M, Okuno Chemical Industries Co., Ltd.). In this way, a laminate (1) was obtained in which the support (E), insulating resin layer (D), resin layer (C), plating underlayer (B), and metal plating layer (F) were laminated in this order.

[0268] Example 2 The glossy side (non-roughened side) of copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of a prepreg (R-5670KG manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and heat-pressed at 195 ° C. for 90 minutes using a hand press ("Mini Test Press" manufactured by Toyo Seiki Seisakusho Co., Ltd.). Then, the copper foil was immersed in a ferric chloride etching solution (content 40 mass%) at 40 ° C. for 3 minutes to etch the entire surface of the copper foil, thereby obtaining a rigid substrate in which the prepreg corresponding to the support (E) was hardened. Then, a corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W) was performed on both sides of the rigid substrate. Next, the surface of the transfer laminate (1) obtained in Preparation Example 6 on which the insulating resin layer (D) was formed was attached to both sides of the rigid base material, and pressure-bonded for 10 minutes at 150° C. using a hand press (Mini Test Press, manufactured by Toyo Seiki Seisakusho Co., Ltd.) After that, only the release PET film was peeled off, thereby forming the insulating resin layer (D), the resin layer (C), and the plating underlayer (B) on both sides of the cured prepreg.

[0269] Thereafter, the above-obtained plating underlayer (B) was set as the cathode side, and phosphorus-containing copper was set as the anode side, and electroplating was performed at a current density of 2 A / dm using an electrolytic plating solution containing copper sulfate. 2For 27 minutes, electrolytic plating was performed at 400 K for 27 minutes to form a copper plating layer (12 μm thick) corresponding to the metal plating layer (F) on the plating underlayer (B). The electrolytic plating solution used was 70 g / L copper sulfate, 200 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additive (Top Lucina SF-M, Okuno Chemical Industries Co., Ltd.). In this way, a laminate (2) was obtained in which the support (E), insulating resin layer (D), resin layer (C), plating underlayer (B), and metal plating layer (F) were laminated in this order.

[0270] Example 3 A laminate (3) was obtained in the same manner as in Example 2, except that the transferred laminate (2) was used in place of the transferred laminate (1) of the laminate (2).

[0271] Example 4 A laminate (4) was obtained in the same manner as in Example 2, except that a transfer laminate (3) was used in place of the transfer laminate (1) of the laminate (2).

[0272] Example 5 A laminate (5) was obtained in the same manner as in Example 2, except that a transfer laminate (4) was used in place of the transfer laminate (1) of the laminate (2).

[0273] Example 6 A laminate (6) was obtained in the same manner as in Example 2, except that a transfer laminate (5) was used in place of the transfer laminate (1) of the laminate (3).

[0274] Example 7 The glossy side (non-roughened side) of copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of a prepreg (R-5670KG manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm), and was thermocompressed at 195 ° C for 90 minutes using a hand press ("Mini Test Press" manufactured by Toyo Seiki Seisakusho Co., Ltd.). Then, the substrate was immersed in a ferric chloride etching solution (content 40 mass%) at 40 ° C for 3 minutes to etch the entire surface of the copper foil, thereby obtaining a rigid substrate in which the prepreg corresponding to the support (E) was hardened. Then, a corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W) was performed on both sides of the rigid substrate. Next, the surface of the transfer laminate (6) obtained in Preparation Example 11 on which the insulating resin layer (D) was formed was attached to both sides of the rigid base material, and pressure-bonded at 195° C. for 75 minutes using a hand press (Mini Test Press, manufactured by Toyo Seiki Seisakusho Co., Ltd.) After that, only the copper foil was peeled off, thereby forming the insulating resin layer (D), the resin layer (C), and the plating underlayer (B) on both sides of the cured prepreg.

[0275] Thereafter, the above-obtained plating underlayer (B) was set as the cathode side, and phosphorus-containing copper was set as the anode side, and electroplating was performed at a current density of 2 A / dm using an electrolytic plating solution containing copper sulfate. 2 For 27 minutes, electrolytic plating was performed at 400 K for 27 minutes to form a copper plating layer (12 μm thick) corresponding to the metal plating layer (F) on the plating underlayer (B). The electrolytic plating solution used was 70 g / L copper sulfate, 200 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additive (Top Lucina SF-M, Okuno Chemical Industries Co., Ltd.). In this way, a laminate (7) was obtained in which the support (E), the insulating resin layer (D), the resin layer (C), the plating underlayer (B), and the metal plating layer (F) were laminated in this order.

[0276] Example 8 A laminate (8) was obtained in the same manner as in Example 7, except that the transferred laminate (7) was used in place of the transferred laminate (6) of the laminate (7).

[0277] Example 9 The surface of the transfer laminate (6) on which the insulating resin layer (D) was formed and the surface of the transfer laminate (8) on which the resin layer (C) was formed were attached to each other and pressure-bonded with a hand press (Mini Test Press, manufactured by Toyo Seiki Seisakusho Co., Ltd.) at 195° C. for 75 minutes. Thereafter, only the copper foil was peeled off to form the insulating resin layer (D), the resin layer (C) and the plating underlayer (B) on both sides of the cured prepreg, and a laminate (9) was obtained in the same manner as in Example 7.

[0278] Example 10 A laminate (10) was obtained in the same manner as in Example 9, except that the transfer laminate (7) was used in place of the transfer laminate (6) of the laminate (9).

[0279] Example 11 Instead of the polyimide film of the laminate (1), a conductive pattern was formed by a subtractive method on a flexible copper-clad laminate (Pyralux TA manufactured by Toray DuPont Co., Ltd.), and an etching resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was attached to the surface of the metal layer (F) at 110 ° C., 0.4 MPa, and 1 m / min, and an exposure process was performed for 2 minutes (316 mJ / cm 2 ) with an exposure machine ("BOX-W10" manufactured by Sanhayato Co., Ltd.), and then the substrate was immersed in a developer (1 mass% sodium carbonate aqueous solution) for 5 minutes to perform a development process to form a pattern resist. Next, the metal layer (F) was dissolved using a copper chloride aqueous solution, and then the substrate was immersed in 3 mass% sodium hydroxide for 3 minutes to peel off the plating resist, and a laminate (11) was obtained in the same manner as in Example 1 using the substrate on which the circuit pattern was formed.

[0280] Example 12 Instead of the prepreg of the laminate (2), a conductive pattern was formed by a subtractive method on a copper-clad laminate (R-5775KH manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm), and an etching resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was attached to the surface of the metal layer (F) at 110 ° C, 0.4 MPa, and 1 m / min, and an exposure process was performed for 2 minutes (316 mJ / cm 2 ) using an exposure machine ("BOX-W10" manufactured by Sanhayato Co., Ltd.), and then the substrate was immersed in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes to perform a development process to form a pattern resist. Next, the metal layer (F) was dissolved using a copper chloride aqueous solution, and then the substrate was immersed in 3 mass % sodium hydroxide for 3 minutes to peel off the plating resist, and a laminate (12) was obtained in the same manner as in Example 2 using the substrate on which the circuit pattern was formed.

[0281] Example 13 A laminate (13) was obtained in the same manner as in Example 12, except that the transfer laminate (2) was used in place of the transfer laminate (1) of the laminate (12).

[0282] Example 14 A laminate (14) was obtained in the same manner as in Example 12, except that the transfer laminate (3) was used in place of the transfer laminate (1) of the laminate (12).

[0283] Example 15 A laminate (15) was obtained in the same manner as in Example 12, except that the transfer laminate (4) was used instead of the transfer laminate (1) of the laminate (12).

[0284] (Example 16) A laminate (16) was obtained in the same manner as in Example 12, except that the transfer laminate (5) was used in place of the transfer laminate (1) of the laminate (12).

[0285] (Example 17) Instead of the prepreg of the laminate (7), a conductive pattern was formed by a subtractive method on a copper-clad laminate (R-5775KH manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm), and an etching resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was attached to the surface of the metal layer (F) at 110 ° C, 0.4 MPa, and 1 m / min, and an exposure process was performed for 2 minutes (316 mJ / cm 2 ) using an exposure machine ("BOX-W10" manufactured by Sanhayato Co., Ltd.), and then the substrate was immersed in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes and developed to form a pattern resist. Next, the metal layer (F) was dissolved using a copper chloride aqueous solution, and then the substrate was immersed in 3 mass % sodium hydroxide for 3 minutes to peel off the plating resist, and a laminate (17) was obtained in the same manner as in Example 7 using the substrate on which the circuit pattern was formed.

[0286] (Example 18) A laminate (18) was obtained in the same manner as in Example 17, except that the transfer laminate (7) was used in place of the transfer laminate (6) of the laminate (17).

[0287] Comparative Example 1 The coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 2 was applied to one side (the first coated side is called side A) of the build-up film (Ajinomoto Co., Inc.'s "GX-92", thickness 50 μm) using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C for 3 minutes to coat a layer corresponding to the resin layer (C) on the build-up film to a thickness of 0.3 μm after drying. Thereafter, the film was turned over, and the coating liquid (1) for forming the plating underlayer (B) obtained in Preparation Example 1 was applied to side A using a small desktop coater (RK Print Coat Instruments' "K Printing Profer") and dried at 180 ° C for 3 minutes to coat a silver layer corresponding to the plating underlayer (B) to a thickness of 0.1 μm after drying. Thereafter, the surface resistance of the plating underlayer (B) became 10000 Ω / □ on side A. A transfer laminate (R1) was prepared.

[0288] Thereafter, the glossy side (non-roughened side) of copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of a prepreg (R-5670KG manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and heat-pressed at 195 ° C. for 90 minutes using a hand press ("Mini Test Press" manufactured by Toyo Seiki Seisakusho Co., Ltd.). Thereafter, the substrate was immersed in a ferric chloride etching solution (content 40 mass%) at 40 ° C. for 3 minutes, and the entire surface of the copper foil was etched to obtain a rigid substrate in which the prepreg corresponding to the support (E) was hardened. Thereafter, a corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W) was performed on both sides of the rigid substrate. Next, the surface of the transfer laminate (R1) on which the build-up film was formed was attached to both surfaces of the rigid substrate, and pressure-bonded at 150° C. for 10 minutes using a hand press ("Mini Test Press" manufactured by Toyo Seiki Seisakusho Co., Ltd.).

[0289] Thereafter, the plating base layer (B) was subjected to copper plating treatment. The plating base layer (B) was set on the cathode side, and phosphorus-containing copper was set on the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 For 40 minutes, electrolytic plating was performed at 1000 K for 40 minutes to form a copper plating layer (12 μm thick) corresponding to the metal plating layer (F) on the plating underlayer (B). The electrolytic plating solution used was 70 g / L copper sulfate, 200 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additive (Top Lucina SF-M, Okuno Chemical Industries Co., Ltd.). In this manner, a laminate (R1) was obtained in which the support (E), the resin layer (C), the plating underlayer (B), and the metal plating layer (F) were laminated in this order.

[0290] Comparative Example 2 Instead of the prepreg of the laminate (R1), a conductive pattern was formed by a subtractive method on a copper-clad laminate (R-5775KH manufactured by Panasonic Corporation, containing glass fiber, thickness 0.1 mm), and an etching resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was attached to the surface of the metal layer (F) at 110 ° C, 0.4 MPa, and 1 m / min, and an exposure process was performed for 2 minutes (316 mJ / cm 2 ) with an exposure machine ("BOX-W10" manufactured by Sanhayato Co., Ltd.), and then the substrate was immersed in a developer (1 mass% sodium carbonate aqueous solution) for 5 minutes and developed to form a pattern resist. Next, the metal layer (F) was dissolved using a copper chloride aqueous solution, and then the substrate was immersed in 3 mass% sodium hydroxide for 3 minutes to peel off the plating resist, and a laminate (R2) was obtained in the same manner as in Comparative Example 1 using the substrate on which the circuit pattern was formed.

[0291] <Normal strength; Evaluation by peel test> The peel strength of the laminates (1) to (10) and (R1) obtained above was measured by a method conforming to IPC-TM-650, NUMBER 2.4.9. The lead width used in the measurement was 1 mm, and the peel angle was 90°. The peel strength tends to be higher as the thickness of the plating layer increases, but the peel strength measurement in the present invention was carried out based on the measured value for a plating layer of 18 μm, which is currently widely used. From the peel strength value before heating measured above, the adhesion was evaluated according to the following criteria. A: The peel strength value is 700N / m or more. B: The peel strength value is 500N / m or more and less than 700N / m. C: The peel strength value is 300 N / m or more and less than 500 N / m. D: The peel strength value is 100 N / m or more and less than 300 N / m. E: The peel strength value is less than 100 N / m.

[0292] <Heat resistance: Evaluation by peel test> The laminates (1) to (10) and (R1) obtained above were placed in a thermostatic chamber at 260° C. for 5 minutes, and the resulting substrates were used to measure peel strength. The peel strength measurement was performed according to a method conforming to IPC-TM-650, NUMBER 2.4.9. The lead width used in the measurement was 1 mm, and the peel angle was 90°. The peel strength tends to be higher as the thickness of the plating layer increases, but the peel strength measurement in the present invention was performed based on the measured value for a plating layer of 18 μm, which is currently widely used. From the peel strength value before heating measured above, the adhesion was evaluated according to the following criteria. A: The peel strength value is 700N / m or more. B: The peel strength value is 500N / m or more and less than 700N / m. C: The peel strength value is 300 N / m or more and less than 500 N / m. D: The peel strength value is 100 N / m or more and less than 300 N / m. E: The peel strength value is less than 100 N / m.

[0293] <Normal test: Evaluation of embedding performance in wiring> The laminates (11) to (18) and (R2) obtained above were used to evaluate the number of voids generated at the interface between the substrate and the wiring and the insulating resin layer by observing the cross section of the wiring with a length of 50 mm and a width of LINE / SPACE = 50 / 50 μm. The number of voids was calculated by observing 10 processed wirings and calculating the average value per wiring. A: The number of voids is 0 or more and less than 2. B: The number of voids is 2 or more and less than 4. C: The number of voids is 4 or more and less than 7. D: The number of voids is 7 or more and less than 10. E: The number of voids is 10 or more.

[0294] <Heat resistance test: Evaluation of embedding performance in wiring> The laminates (11) to (18) and (R2) obtained above were placed in a thermostatic chamber at 260°C for 60 minutes, and then the number of voids generated at the interface between the substrate and the wiring and the insulating resin layer was evaluated by observing the cross section of the wiring with a length of 50 mm and a width of LINE / SPACE = 50 / 50 μm. The number of voids was calculated by observing 10 processed wirings and calculating the average value per one. A: The number of voids is 0 or more and less than 2. B: The number of voids is 2 or more and less than 4. C: The number of voids is 4 or more and less than 7. D: The number of voids is 7 or more and less than 10. E: The number of voids is 10 or more.

[0295] The evaluation results of the adhesion and wiring embeddability of Examples 1 to 18 and Comparative Examples 1 and 2 are shown in Tables 1 and 2.

[0296] In Examples 1 to 18, a resin layer (C) and an insulating resin layer (D) were formed, and both the adhesion and the wiring embedding performance showed good results.

[0297] On the other hand, in Comparative Example 1, heat was applied to the semi-cured build-up film during the coating drying process of the plating underlayer (B) and the resin layer (C), resulting in poor adhesion between the build-up film and the substrate, and poor wiring embedding performance.

[0298] [Table 1]

[0299] [Table 2] [Explanation of symbols]

[0300] 1: Temporary support 2: Plating base layer 3: Resin layer 4: Insulating resin layer 5: Base material 6: Metal plating layer 7: Metal layer

Claims

1. A laminate comprising a temporary support (A) and, on at least one surface thereof, a plating underlayer (B) containing a dispersant (b1) and a conductive material (b2), a resin layer (C), and an insulating resin layer (D) having a THF solution insoluble content of 1 to 80% by weight.

2. 2. The laminate according to claim 1, wherein the surface of the laminate on which the insulating resin layer (D) is formed is attached to at least one surface of a support (E).

3. 2. The laminate according to claim 1, further comprising a resin layer (C), a plating underlayer (B), and a temporary support (A) on both sides of the insulating resin layer (D) in that order.

4. 3. The laminate according to claim 1, further comprising a metal plating layer (F) on the plating underlayer (B) of the laminate.

5. The laminate according to claim 1 or 2, characterized in that the resin layer (C) is a compound (c1) having a functional group [X] and the insulating resin layer (D) is a compound (d1) having a functional group [Y], thereby forming a chemical bond.

6. 3. The laminate according to claim 1, wherein the functional group [X] contained in the resin layer (C) has at least one of an epoxy group and an amino group.

7. 3. The laminate according to claim 1, wherein the functional group [Y] contained in the insulating resin layer (D) has at least one of an epoxy group, a maleimide group, a vinylbenzyl group, an acrylate group, a methacrylate group, a carbonyl group, and a hydroxyl group.

8. 3. The laminate according to claim 1, wherein the insulating resin layer (D) contains an inorganic compound (x).

9. 3. The laminate according to claim 1, wherein the plating underlayer (B) is one or more layers.

10. 3. The laminate according to claim 1, wherein the resin layer (C) is one or more layers.

11. 3. The laminate according to claim 1, wherein the insulating resin layer (D) is one or more layers.

12. 3. The laminate according to claim 1, wherein the resin layer (C) has a glass transition temperature (Tg) higher than the insulating resin layer (D).

13. 3. The laminate according to claim 1, wherein the dispersant (b1) has a basic nitrogen atom-containing group.

14. 3. The laminate according to claim 1, wherein the conductive material (b2) is silver.

15. The thickness of the plating underlayer (B) is 1 to 10,000 mg / m 2 3. The laminate according to claim 1 or 2,

16. 3. The laminate according to claim 1, wherein the resin layer (C) has a thickness of 0.01 to 100 μm.

17. 3. The laminate according to claim 1, wherein the insulating resin layer (D) has a thickness of 1 to 1000 μm.

18. 5. The laminate according to claim 4, wherein the thickness of the metal plating layer (F) is 0.05 to 1000 μm.

19. A plating underlayer (B), a resin layer (C) and an insulating resin layer (D) are sequentially formed on a temporary support (A). A method for manufacturing a laminate.

20. A plating underlayer (B), a resin layer (C) and an insulating resin layer (D) are sequentially formed on a temporary support (A). Step 1 for producing a laminate; A step 2 of bonding the surface of the laminate on which the insulating resin layer (D) is formed to at least one surface of a support (E); A step 3 of peeling off the temporary support (A) of the laminate bonded to the support (E) and forming the insulating resin layer (D), the resin layer (C) and the plating underlayer (B) on at least one surface of the support (E); Step 4 of forming a metal plating layer (F) on the surface of the plating underlayer (B); The method for producing a laminate according to claim 1 or 2, further comprising the steps of:

21. A printed wiring board, a package substrate, an interposer, a wiring substrate for LED electrodes, and an optoelectronic device, comprising the laminate according to claim 1 or 2.

Citation Information

Patent Citations

  • Film with metal film

    WO2010024370A1

  • Laminated body, printed wiring board using same, flexible printed wiring board, and molded article

    WO2019013038A1